Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element

By developing a liquid crystal alignment agent composed of a specific polymer, the problem of decreasing adhesion of the liquid crystal alignment film after low temperature sintering is solved, and a liquid crystal alignment film that maintains good adhesion under low temperature conditions is realized, which is suitable for the manufacturing of flexible liquid crystal representation elements.

CN119614213APending Publication Date: 2025-03-14NISSAN CHEM CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411849305.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-12-28
Filing Date
2017-12-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the adhesion of the liquid crystal orientation film after low temperature sintering is significantly reduced, making it difficult to meet the requirements of the flexible liquid crystal representation element for high adhesion.

Method used

A liquid crystal alignment agent containing a specific polymer composition is developed, which can maintain good adhesion under low temperature sintering conditions. The liquid crystal aligning agent contains polymers such as polyimide, polyamic acid, polyamic acid ester, and monomers having polymerizable unsaturated bonds. The adhesion of the liquid crystal aligning film is improved by combining a specific compound and a diamine.

Benefits of technology

It is realized that a liquid crystal alignment film that can maintain good adhesion even under low temperature sintering conditions is suitable for the manufacturing of flexible liquid crystal display elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614213A_ABST
    Figure CN119614213A_ABST
Patent Text Reader

Abstract

The invention relates to a liquid crystal aligning agent, a liquid crystal alignment film and a liquid crystal display element. Provided are: a liquid crystal alignment film which has good adhesion even after a low-temperature firing process; a liquid crystal alignment agent which forms the liquid crystal alignment film; and a liquid crystal display element which is provided with the liquid crystal alignment film. The present invention provides a liquid crystal aligning agent containing: component (A) below; component (B) below; and (C) component; and an organic solvent. Component (A): a polymer such as a polyimide, a polyamic acid, or a polyamic acid ester. Component (B): at least one compound selected from the group consisting of compounds represented by formula [CL-1] and compounds represented by formula [CL-2]. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with the application date of December 27, 2017, application number 201780087533.X, and invention name “Liquid Crystal Alignment Agent, Liquid Crystal Alignment Film and Liquid Crystal Display Element”. Technical Field

[0002] The present invention relates to a liquid crystal aligning agent having good adhesion even when a low-temperature calcining process is used, a liquid crystal aligning film obtained from the liquid crystal aligning agent, and a liquid crystal display element including the liquid crystal aligning film. Background Art

[0003] Flexible liquid crystal display elements using a flexible resin film as a substrate have various advantages, such as being thin and lightweight, or being foldable so as to be storable and movable, and are suitable for viewing and listening to digital contents now and in the near future.

[0004] However, since resin films lack heat resistance, low-temperature processes for producing various elements constituting liquid crystal display elements, such as liquid crystal alignment films, have been proposed, and a liquid crystal alignment film material capable of low-temperature sintering has been required (Patent Document 1).

[0005] In addition, since a resin film is generally less susceptible to external impact than a glass substrate, high adhesion is required between the alignment film and the resin film substrate.

[0006] The inventors of the present invention studied the conventional liquid crystal alignment agent containing a crosslinking agent and found that the adhesion of the liquid crystal alignment film obtained by low-temperature calcination was significantly reduced. Therefore, it is desired to develop a liquid crystal alignment agent and a liquid crystal alignment film having good adhesion even when calcined at a low temperature.

[0007] For example, Patent Document 2 and the like report a composition suitable for forming a cured film having liquid crystal orientation. In addition, for example, Patent Document 3 discloses a liquid crystal orientation film having polycarbonate as an essential component. However, these documents are not sufficient for the purpose of providing a liquid crystal orientation agent having good adhesion even when calcined at a low temperature.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: WO2012 / 121259

[0011] Patent Document 2: WO2015 / 129890

[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 11-119225 Summary of the invention

[0013] Problem that the invention aims to solve

[0014] Therefore, an object of the present invention is to provide a liquid crystal alignment film having good adhesion even after a low-temperature calcination step, a liquid crystal aligning agent for forming the liquid crystal alignment film, and a liquid crystal display element including the liquid crystal alignment film.

[0015] In addition to the above object, another object of the present invention is to provide a method for producing the above liquid crystal alignment film.

[0016] Solutions for solving problems

[0017] The present inventors have found the following invention.

[0018] <1> A liquid crystal alignment agent, comprising:

[0019] (A) at least one polymer selected from the group consisting of polyimide, polyamic acid, polyamic acid ester, polyorganosiloxane, polyester, polyamide, and a polymerizable unsaturated bond-containing monomer;

[0020] (B) at least one compound selected from the group consisting of a compound represented by the following formula [CL-1] and a compound represented by the following formula [CL-2], wherein:

[0021] In formula [CL-1], r 1 represents a hydrogen atom or a methyl group,

[0022] r 2 represents a linear or branched alkylene group having 2 to 20 carbon atoms, a divalent organic group consisting of an aliphatic ring having 5 to 6 carbon atoms, or a divalent aliphatic group containing an aliphatic ring having 5 to 6 carbon atoms, wherein -CH 2 - is optionally replaced by -O-,

[0023] r 3 represents a k-valent linear or branched aliphatic group having 2 to 20 carbon atoms, a k-valent group formed by an aliphatic ring having 5 to 6 carbon atoms, or a k-valent aliphatic group containing an aliphatic ring having 5 to 6 carbon atoms, wherein -CH 2 - is optionally replaced by -O-,

[0024] Z represents a divalent group represented by the following formula (1a),

[0025] In formula (1a), r 4 represents a linear or branched alkyl group having 1 to 20 carbon atoms, a monovalent group consisting of an aliphatic ring having 5 to 6 carbon atoms, or a monovalent aliphatic group containing an aliphatic ring having 5 to 6 carbon atoms, wherein -CH 2 - is optionally replaced by -O-,

[0026] In *1 and *2, one represents a bond to a nitrogen atom, and the other represents a bond to r 3 , k is a natural number greater than or equal to 2 and less than or equal to 9;

[0027] In the formula [CL-2], R CL1 is a hydrogen atom or a methyl group,

[0028] R CL2 and R CL3 are independently a hydrogen atom, a linear or branched alkyl group having 1 to 20 carbon atoms, or a linear or branched hydroxyalkyl group having 1 to 20 carbon atoms,

[0029] R CL4 is hydroxy or a linear or branched hydroxyalkyl group having 1 to 20 carbon atoms; and

[0030] (C) Organic solvent.

[0031]

[0032] Effects of the Invention

[0033] According to the present invention, a liquid crystal alignment film having good adhesion even after a low-temperature calcination step, a liquid crystal aligning agent for forming the liquid crystal alignment film, and a liquid crystal display element including the liquid crystal alignment film can be provided.

[0034] Moreover, according to this invention, in addition to the said effect, the manufacturing method of the said liquid crystal alignment film can be provided. DETAILED DESCRIPTION

[0035] The present application provides a liquid crystal aligning agent, a liquid crystal aligning film obtained from the liquid crystal aligning agent, and a liquid crystal display element including the liquid crystal aligning film.

[0036] <Liquid Crystal Alignment Agent>

[0037] The liquid crystal aligning agent of the present application contains (A) component, (B) component, and (C) component: an organic solvent.

[0038] <<(A)Ingredient>>

[0039] (A) Component is at least one polymer selected from the group consisting of polymers of polyimide, polyamic acid, polyamic acid ester, polyorganosiloxane, polyester, polyamide, and monomers having a polymerizable unsaturated bond.

[0040] The component (A) will be described in detail below.

[0041] [Polyamic acid]

[0042] The polyamic acid used in the present invention can be obtained by reacting a diamine compound with tetracarboxylic dianhydride.

[0043] <Diamine>

[0044] The diamine used for polymerization of the polyamic acid of the present invention can be generally represented by the following formula (1).

[0045]

[0046] A in the above formula (1) 1 and A 2 are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an alkynyl group having 2 to 5 carbon atoms, and Y 1 A1 and A2 are preferably a hydrogen atom or a methyl group from the viewpoint of liquid crystal orientation.

[0047] As a preferred embodiment of the formula (1), a diamine of the following formula (DA-1) is used as the diamine.

[0048]

[0049] In the above formula (DA-1), Y d It is a divalent organic group represented by the following formula (Y-1) to (Y-171).

[0050]

[0051]

[0052] In formula (Y-87), X 1 is a sulfur atom, an oxygen atom or -NH-, R 8 and R 9 are independently a divalent organic group, R 8 and R 9 At least one of the two has an aromatic ring, "-CO-X 1 At least one of the connecting bonds in "-" is bonded to an aromatic ring, and is preferably a group formed by removing two amino groups from compounds of formulae (b-1) to (b-42) described in paragraphs

[0047] to

[0048] of Publication No. 2015-135464.

[0053]

[0054] In formula (Y-139), R 1 , R 2 They are ethylene, -COO-, -OCO-, -NHCO-, -N(CH 3 )CO-.

[0055]

[0056]

[0057] It should be noted that, in the above formula, n is an integer of 1-6.

[0058] As a preferred embodiment of the diamine that can be used in the present invention, diamines having an alkyl group or a fluorinated alkyl group in a side chain represented by the following formula [Sd-1] to [Sd-4] can be mentioned.

[0059]

[0060] In the formula, A 1 Each independently represents an alkyl group having 1 to 22 carbon atoms or a fluorine-containing alkyl group having 1 to 22 carbon atoms.

[0061] Another preferred embodiment of the diamine that can be used in the present invention includes 2,4-diaminobenzoic acid, 2,5-diaminobenzoic acid, 3,5-diaminobenzoic acid, 4,4'-diaminobiphenyl-3,3'-dicarboxylic acid, 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid, 3,3'-diaminobiphenyl-4,4'-dicarboxylic acid, 3,3'-diaminobiphenyl-2,4'-dicarboxylic acid, 4,4'-diaminodiphenylmethane-3,3'-dicarboxylic acid, 4,4'-diaminobiphenyl-3-carboxylic acid, 4,4'-diaminodiphenylmethane-3-carboxylic acid, 4,4'-diaminodiphenylethane-3,3'-dicarboxylic acid, 4,4'-diaminodiphenylethane-3-carboxylic acid, 4,4'-diaminodiphenyl ether-3,3'-dicarboxylic acid, and diamines having structures represented by the following formulas [4a-1] to [4a-6]. The above diamines are preferred in terms of increasing the curing speed of the liquid crystal alignment film, and are more preferably used together with the diamines for imparting vertical alignment described below. The diamines are preferably 10 mol% or more, more preferably 20 mol% or more, relative to the total diamine component used in the liquid crystal alignment agent.

[0062]

[0063] As another preferred embodiment of the diamine that can be used in the present invention, diamines represented by the following formula [2a-1] to [2a-9] (n each independently represents an integer of 2 to 12) are mentioned.

[0064]

[0065] As another preferred embodiment of the diamine that can be used in the present invention, a diamine having a heterocyclic ring represented by the following formula (bs) can be mentioned.

[0066]

[0067] In the above formula [bs],

[0068] X 1 is selected from -O-, -NQ1-, -CONQ1-, -NQ1CO-, -CH 2 at least one divalent organic group selected from the group consisting of -O- and -OCO-, Q1 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms,

[0069] X 2 is a single bond, or at least one divalent organic group selected from the group consisting of an aliphatic hydrocarbon group having 1 to 20 carbon atoms, a non-aromatic hydrocarbon group, and an aromatic hydrocarbon group,

[0070] X 3 is a single bond, or is selected from -O-, -NQ2-, -CONQ2-, -NQ2CO-, -COO-, -OCO- and -O(CH 2 )m-(m is an integer from 1 to 5), Q2 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms,

[0071] X 4 is a nitrogen-containing aromatic heterocycle, n is an integer of 1 to 4, and is preferably a combination described in Tables 1 to 3 in paragraphs

[0036] to

[0038] of International Publication WO2009 / 093707.

[0072] As another preferred embodiment of the diamine that can be used in the present invention, a diamine having a photoreactive group represented by the following formula (PV-0) can be mentioned.

[0073]

[0074] In the above formula (PV-0), X 2 represents a substituent and is a group having a structure represented by the following formula (2A) or the following formula (2B).

[0075]

[0076] In the above formula (2A) and the above formula (2B), R represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms (wherein any hydrogen atom thereof may be substituted by a fluorine atom), or an alkoxy group having 1 to 18 carbon atoms (wherein any hydrogen atom thereof may be substituted by a fluorine atom). A and B each independently represent a single bond or any ring structure represented by the following formula. Wherein any hydrogen atom in the ring structure may be substituted by an alkoxy group having 1 to 10 carbon atoms. T 1 ~T 4 Each independently represents a single bond, an ether, an ester, an amide or a keto bond. S represents a single bond or an alkylene group having 1 to 10 carbon atoms.

[0077] In the case of imparting vertical alignment, as diamines that can be used in the present invention, there can be listed diamines represented by formulas [2-1] to [2-31] described in paragraphs

[0033] to

[0042] of International Publication WO2013 / 125595, and the like, relative to the entire diamine component, these diamines are preferably set to 5 mol% or more, more preferably set to 10 mol% or more, and further preferably set to 20 mol% or more. From the perspective of increasing the curing speed, it is preferably 90 mol% or less, and more preferably 80 mol% or less. More preferably, the diamine is at least one selected from the following formulas [2a-24] to [2a-33].

[0078]

[0079] In formula (2a-32), when R is ortho to an amino group, 1 Each independently represents a member selected from -O-, -OCH 2 -、-CH 2 O-、-COOCH 2 -and-CH 2 When at least one linking group in OCO- is meta to the two amino groups, in addition to the linking groups shown above, R 1 It also represents a group selected from -CONH-, -NHCO- and -CH 2 - at least one linking group; R 2 Each independently represents a linear or branched alkyl group having 1 to 22 carbon atoms or a linear or branched alkoxy group having 1 to 22 carbon atoms; Cy is a group selected from 4,4'-biphenyldiyl, 4,4'-phenylcyclohexyl and 4,4'-dicyclohexyl.

[0080]

[0081] In the above formula, R 3 Indicates -O- or -CH 2 O-, Cy2 is synonymous with the above Cy; R 7 Each independently represents a linear or branched alkyl group having 3 to 12 carbon atoms, and the cis-trans isomerism of 1,4-cyclohexylene represents a trans isomer.

[0082] Moreover, in addition to the diamines listed above, 4-(2-(methylamino)ethyl)aniline or the diamines described in JP-A-2010-97188 can also be used.

[0083] Among the above-mentioned photoreactive diamines, the following compounds are preferred from the viewpoint of photoreactivity and the like.

[0084]

[0085] The C of the particularly preferred diamine compound exemplified in the above formulas is n H 2n+1 In the part, n represents an integer of 0 to 18.

[0086] <Tetracarboxylic dianhydride>

[0087] Examples of the tetracarboxylic dianhydride include aliphatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride, aromatic tetracarboxylic dianhydride, etc. Specific examples thereof include tetracarboxylic dianhydrides of the following groups [1] to [5].

[0088] Examples of the aliphatic tetracarboxylic dianhydride include: [1] 1,2,3,4-butanetetracarboxylic dianhydride;

[0089] [2] As the alicyclic tetracarboxylic dianhydride, for example, the following formulas (X1-1) to (X1-13) (in the formulas (X1-1) to (X1-4), R 3 To R 23 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, or a phenyl group, and they may be the same or different,

[0090] In the formula, R M is a hydrogen atom or a methyl group,

[0091] Xa is a tetravalent organic group represented by the following formula (Xa-1) to (Xa-7)) or an acid dianhydride;

[0092]

[0093]

[0094] [3] 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 3-oxabicyclo[3.2.1]octane-2,4-dione-6-spiro-3'-(tetrahydrofuran-2',5'-dione), 3,5,6-tricarboxy-2-carboxymethylnorbornane-2:3,5:6-dianhydride, 4,9-dioxatricyclo[5.3.1.02,6]undecane-3,5,8,10-tetraone, etc.;

[0095] [4] Aromatic tetracarboxylic dianhydrides such as 1,2,4,5-pyromellitic anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, and acid dianhydrides represented by the following formulas (Xb-1) to (Xb-10); and

[0096]

[0097] [5] Furthermore, acid dianhydrides represented by formulas (X1-44) to (X1-52) and tetracarboxylic dianhydrides described in JP-A-2010-97188.

[0098]

[0099] In addition, the said tetracarboxylic dianhydride can be used individually by 1 type or in combination of 2 or more types.

[0100] <Production Method of Polyamic Acid>

[0101] The polyamic acid used in the present invention can be synthesized by a known method (for example, see International Publication No. WO2014 / 034792).

[0102] From the perspective of solubility of monomers and polymers, the organic solvent used in the above reaction is preferably N,N-dimethylformamide, N-methyl-2-pyrrolidone, or γ-butyrolactone, and these can be used alone or in combination. From the perspective of not easily precipitating the polymer and easily obtaining a high molecular weight body, the concentration of the polymer is preferably 1 to 30% by mass, more preferably 5 to 20% by mass.

[0103] [Polyamic acid ester]

[0104] The polyamic acid ester used in the present invention can be obtained as follows.

[0105] <Production method of polyamic acid ester>

[0106] The polyamic acid ester used in the present invention can be synthesized by any of the following known methods (for example, see International Publication No. WO2014 / 034792): (1) synthesized from polyamic acid, (2) synthesized from tetracarboxylic acid diester and diamine, or (3) synthesized by reacting tetracarboxylic acid diester dichloride with diamine.

[0107] As the tetracarboxylic acid diester, the following reaction formula (wherein, R 1 is an alkyl group having 1 to 5 carbon atoms, and A is a tetravalent organic group derived from the tetracarboxylic dianhydride. 1 It can be produced by a known method of reacting an alcohol having 1 to 5 carbon atoms represented by OH (see, for example, International Publication No. 2010 / 092989).

[0108]

[0109] Among the tetracarboxylic acid diesters of the present invention, the compounds shown in [5-p-1] are preferred from the viewpoint of obtaining polyamic acid ester having a high molecular weight and low dispersion.

[0110] The tetracarboxylic acid diester dichloride can be produced, for example, by a known method of chlorinating the above-mentioned tetracarboxylic acid dialkyl ester (see, for example, International Publication No. WO2010 / 092989).

[0111] From the viewpoint of obtaining a polyamic acid ester having a high molecular weight and low dispersion, the tetracarboxylic acid diester dichloride is preferably a compound represented by the formula [5-Cl] (in the above formula (5-Cl), A has the same meaning as A in the above formula (5)).

[0112]

[0113] From the viewpoint of solubility of polyamic acid ester, the solvent used in the above reaction is preferably N-methyl-2-pyrrolidone or γ-butyrolactone, and these can be used alone or in combination of two or more. From the viewpoint of not easily precipitating the polymer and easily obtaining a high molecular weight body, the polymer concentration during synthesis is preferably 1 to 30% by mass, more preferably 5 to 20% by mass.

[0114] Among the three methods for synthesizing polyamic acid ester described above, the synthesis method of (2) or (3) described above is particularly preferred because high molecular weight polyamic acid ester can be obtained.

[0115] [Polyimide]

[0116] The polyimide used in the present invention can be obtained by a known method (see, for example, International Publication No. WO2013 / 125595).

[0117] The above-mentioned polyimide can be a completely imidized product obtained by dehydrating and ring-closing all the amic acid structures possessed by polyamic acid or the amic acid ester structures possessed by polyamic acid ester, or it can be a partially imidized product in which only a part of the amic acid or amic acid ester structure is dehydrated and ring-closed, and the amic acid structure or amic acid ester structure and the imide ring structure coexist. For the polyimide used, the imidization rate is preferably 20% or more, and from the perspective of ensuring solubility relative to the solvent, it is preferably 90% or less, and more preferably 60% or less. The imidization rate is a value expressed as a percentage of the total amount of the number of amic acid structures or amic acid ester structures relative to the number of imide ring structures and the proportion of the number of imide ring structures. Here, a part of the imide ring may be an isoimide ring.

[0118] [Polysiloxane]

[0119] The polyorganosiloxane of the present invention can be obtained, for example, by a known method of hydrolyzing and condensing a hydrolyzable silane compound (see, for example, International Publication No. WO2009 / 025386).

[0120] Examples of the silane compound used for the synthesis of the polyorganosiloxane include: alkoxysilane compounds such as tetramethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and dimethyldiethoxysilane; nitrogen- and sulfur-containing alkoxysilane compounds such as 3-mercaptopropyltriethoxysilane, mercaptomethyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-(3-cyclohexylamino)propyltrimethoxysilane; 3-glycidoxypropyltrimethoxysilane, 3- Silane compounds containing epoxy groups such as glycidoxypropyl triethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, and 2-(3,4-epoxycyclohexyl) ethyl triethoxysilane; alkoxysilane compounds containing unsaturated bonds such as 3-(meth)acryloxypropyl trimethoxysilane, 3-(meth)acryloxypropyl methyl dimethoxysilane, 3-(meth)acryloxypropyl methyl diethoxysilane, and vinyl triethoxysilane; trimethoxysilylpropyl succinic anhydride, etc. For the hydrolyzable silane compound, one of these may be used alone or two or more may be used in combination. It should be noted that "(meth)acryloxy" means including "acryloxy" and "methacryloxy".

[0121] The polyorganosiloxane of the present invention has a polystyrene-equivalent weight average molecular weight (Mw) measured by GPC, preferably in the range of 100 to 50,000, and more preferably in the range of 200 to 10,000.

[0122] Among the polyorganosiloxanes of the present invention, polyorganosiloxanes having a repeating unit represented by the following formula (P-Si-Ep) are preferred.

[0123]

[0124] In the formula (P-Si-Ep), X 1 The following formula (X 1 -1) or (X 1 -2) (wherein "*" represents a connecting bond.) epoxy group, Y 1 It is a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms.

[0125]

[0126] In the polyorganosiloxane of the present invention, from the viewpoint of achieving the effects of the present invention, it is preferable to use the following cinnamic acid derivative (Cn-1) or (Cn-2) as the carboxylic acid having a liquid crystal alignment group.

[0127]

[0128] [Polyester]

[0129] The polyester used in the present invention can be obtained, for example, by reacting a dicarboxylic acid with a diepoxy compound. Here, the diepoxy compound includes, in addition to ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, and 1,6-hexanediol diglycidyl ether, diepoxy compounds described in Japanese Patent Application Laid-Open No. 2013-113937 and the like.

[0130] The ratio of the diepoxy compound to the dicarboxylic acid compound used in the synthesis reaction of the polyester is preferably 0.2 to 2 equivalents, more preferably 0.3 to 1.2 equivalents, of epoxy groups of the diepoxy compound per 1 equivalent of carboxyl groups contained in the dicarboxylic acid compound.

[0131] The reaction of the dicarboxylic acid and the diepoxide is preferably carried out in the presence of an organic solvent. Examples of the organic solvent used include aprotic polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, N,N-dimethylimidazolidinone, dimethyl sulfoxide, γ-butyrolactone, tetramethylurea, and hexamethylphosphoric triamide; and phenolic solvents such as m-cresol, xylenol, phenol, and halogenated phenol.

[0132] In this way, a solution containing polyester as polymer (A) can be obtained. The reaction solution can be directly used for the preparation of a liquid crystal alignment agent, or can be used for the preparation of a liquid crystal alignment agent after separating the polyester contained in the reaction solution, or can be used for the preparation of a liquid crystal alignment agent after purifying the separated polyester. The separation and purification of the polyester can be carried out according to a known method.

[0133] The polyester obtained as described above preferably has a polystyrene-equivalent number average molecular weight (Mn) measured by GPC of 250 to 500,000, more preferably 500 to 100,000, and even more preferably 1,000 to 50,000, from the viewpoint of making the liquid crystal orientation of the formed liquid crystal orientation film good and ensuring the temporal stability of the liquid crystal orientation.

[0134] [Polyamide]

[0135] The polyamide used in the present invention can be obtained, for example, by a method of reacting a dicarboxylic acid with a diamine, etc. Here, it is preferred that the dicarboxylic acid is chlorinated using an appropriate chlorinating agent such as thionyl chloride and then subjected to the reaction with the diamine.

[0136] There are no particular restrictions on the dicarboxylic acids used in the synthesis of polyamides, and examples thereof include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, and fumaric acid; dicarboxylic acids having an alicyclic structure such as cyclobutane dicarboxylic acid and cyclohexane dicarboxylic acid; and dicarboxylic acids having an aromatic ring such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 4,4'-carbonyl dibenzoic acid, 4-carboxycinnamic acid, and terephthalic acid. It should be noted that the dicarboxylic acids may be used alone or in combination of two or more.

[0137] By using at least a portion of the diamine used in the above-mentioned polyimide precursor as the diamine used in the synthesis of the polyamide of the present invention, a polyamide can be obtained. It should be noted that during the synthesis, other diamines can be used in combination as needed. One diamine can be used alone or in combination of two or more.

[0138] The ratio of dicarboxylic acid and diamine used in the synthesis reaction of polyamide is preferably 0.2 to 2 equivalents of carboxyl groups of dicarboxylic acid relative to 1 equivalent of amino groups of diamine. The reaction of dicarboxylic acid (preferably chlorinated dicarboxylic acid) and diamine is preferably carried out in an organic solvent in the presence of a base. As an organic solvent, for example, tetrahydrofuran, dioxane, toluene, chloroform, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, etc. can be preferably used. The amount of organic solvent is preferably set to 400 to 900 parts by weight relative to 100 parts by weight of the total amount of dicarboxylic acid and diamine. As a base for the above reaction, for example, tertiary amines such as pyridine, triethylamine, N-ethyl-N,N-diisopropylamine can be preferably used. The amount of base is preferably set to 2 to 4 moles relative to 1 mole of diamine.

[0139] As described above, a reaction solution in which polyamide is dissolved can be obtained. This reaction solution may be used for preparation of a liquid crystal aligning agent as it is, or may be used for preparation of a liquid crystal aligning agent after isolating polyamide contained in the reaction solution.

[0140] The polyamide of the present invention has a polystyrene-equivalent weight average molecular weight (Mw) measured by GPC of preferably 1,000 to 500,000, more preferably 5,000 to 300,000.

[0141] [Polymer of monomer having polymerizable unsaturated bond]

[0142] In the polymer of a monomer having a polymerizable unsaturated bond (hereinafter also referred to as a "polymer (PAc)"), examples of the polymerizable unsaturated bond possessed by the monomer include: (meth)acryloyl, vinyl, styryl, maleimide, etc. Specific examples of such monomers having a polymerizable unsaturated bond include: unsaturated carboxylic acids such as (meth)acrylic acid, α-ethylacrylic acid, maleic acid, fumaric acid, and vinylbenzoic acid; (meth)acrylic acid alkyl (meth)acrylic acid cycloalkyl esters, benzyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, trimethoxysilylpropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, glycidyl (meth)acrylate, 3,4-epoxy (meth)acrylate. Unsaturated carboxylates such as cyclohexyl methyl ester, (meth) acrylate 3,4-epoxybutyl ester, acrylate 4-hydroxybutyl glycidyl ether; (meth) acrylic acid compounds such as unsaturated polycarboxylic anhydrides such as maleic anhydride; aromatic vinyl compounds such as styrene, methyl styrene, divinylbenzene; conjugated diene compounds such as 1,3-butadiene, 2-methyl-1,3-butadiene; maleimide-containing compounds such as N-methylmaleimide, N-cyclohexylmaleimide, and N-phenylmaleimide. It should be noted that the monomer having a polymerizable unsaturated bond can be used alone or in combination of two or more.

[0143] From the viewpoint of transparency, material strength, etc., as the polymer (PAc), among the above, a polymer containing a monomer of a (meth)acrylic acid compound is preferred. When synthesizing the polymer (PAc), the proportion of the (meth)acrylic acid compound used is preferably 50 mol% or more, more preferably 60 mol% or more, and further preferably 70 mol% or more relative to the total amount of monomers used in the synthesis.

[0144] When producing a vertical alignment type liquid crystal display element, a photoreactive monomer represented by the structure of the following formula (3m)-1 may be used.

[0145]

[0146] In formula (3m)-1, Mc represents a polymerizable unsaturated bond such as a (meth)acryloyl group, a vinyl group, a styryl group, or a maleimide group.

[0147] Sb is a linear or branched alkylene group having 1 to 10 carbon atoms, a divalent aromatic group or a divalent alicyclic group,

[0148] Md is a single bond, a divalent heterocycle, a trivalent heterocycle, a tetravalent heterocycle, a substituted or unsubstituted branched alkyl group having 1 to 10 carbon atoms, a divalent aromatic group, a trivalent aromatic group, a tetravalent aromatic ring, a divalent alicyclic group, a trivalent alicyclic group, a tetravalent alicyclic group, a divalent condensed ring group, a trivalent condensed ring group or a tetravalent condensed ring group, each of which is unsubstituted or one or more hydrogen atoms are optionally substituted by a fluorine atom, a chlorine atom, a cyano group, a methyl group or a methoxy group,

[0149] d is an integer of 1 to 3, and Z is an oxygen atom or a sulfur atom.

[0150] Xa and Xb are each independently a hydrogen atom, a fluorine atom, a chlorine atom, a cyano group or an alkyl group having 1 to 3 carbon atoms,

[0151] R 1 is a single bond, an oxygen atom, -COO- or -OCO-, preferably a single bond, -COO- or -OCO-,

[0152] R 2 is a divalent aromatic group, a divalent alicyclic group, a divalent heterocyclic group or a divalent condensed ring group,

[0153] R 3 is a single bond, an oxygen atom, -COO- or -OCO-,

[0154] R 4 is a linear or branched alkyl group having 1 to 40 carbon atoms or a monovalent organic group having 3 to 40 carbon atoms including an alicyclic group,

[0155] R 5 is an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorine atom or a cyano group, preferably a methyl group, a methoxy group or a fluorine atom,

[0156] a is an integer of 0-3, and b is an integer of 0-4.

[0157] Examples of the monomer represented by the above formula (3m)-1 include the following monomers, but are not limited to these.

[0158]

[0159]

[0160] The ratio of the photoreactive monomer to be used is preferably 10 to 95 mol%, more preferably 10 to 90 mol%, and further preferably 20 to 70 mol%, based on the total amount of monomers used for synthesis.

[0161] The polymer (PAc) can be obtained, for example, by polymerizing a monomer having an unsaturated bond of a polymerizable group in the presence of a polymerization initiator. As the polymerization initiator used, for example, azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) are preferred. The use ratio of the polymerization initiator is preferably set to 0.01 to 30 parts by mass relative to 100 parts by mass of all monomers used for the reaction. The above-mentioned polymerization reaction is preferably carried out in an organic solvent. As the organic solvent used for the reaction, for example, alcohols, ethers, ketones, amides, esters, hydrocarbon compounds, etc. are listed, preferably diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether acetate, etc. For the amount (a) of the organic solvent used, it is preferably set to an amount that makes the total amount (b) of the monomers used in the reaction 0.1 to 60% by mass relative to the total amount (a+b) of the reaction solution.

[0162] According to a preferred embodiment of the present invention, the component (A) is at least one polymer selected from the group consisting of polyimide, polyamic acid, polyamic acid ester, and polymerizable unsaturated bond-containing monomer polymers.

[0163] According to a more preferred embodiment of the present invention, component (A) is a polymer obtained by reacting a tetracarboxylic acid derivative with a diamine, and the tetracarboxylic acid derivative is at least one selected from the group consisting of tetracarboxylic dianhydride, tetracarboxylic acid diester and tetracarboxylic acid diester dichloride. In this case, the tetracarboxylic dianhydride, tetracarboxylic acid diester and tetracarboxylic acid diester dichloride preferably include at least one structure selected from the group consisting of the aliphatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride, aromatic tetracarboxylic dianhydride, and their tetracarboxylic acid diester and tetracarboxylic acid diester dichloride.

[0164] More preferably, the ring structure includes at least one structure selected from the group consisting of a cyclobutane ring structure, a cyclopentane ring structure, a cyclohexane ring structure, and a benzene ring structure. Specifically, from the perspective of solubility of polyamic acid, polyamic acid ester, or polyimide obtained by imidizing them in solvents, preferred are the formulas (X1-1) to (X1-3), (X1-6) to (X1-12), (Xa-1) to (Xa-2), 1,2,4,5-pyromellitic anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, (Xb-6) to (Xb-8), (X1-44), (X1-47) to (X1-52), and more preferred examples include: (X1-1) to (X1-3), (X1-6) to (X1-12), (Xa-1) to (Xa-2), (Xb-6) to (Xb-8), (X1-44), and (X1-49).

[0165] As a more preferred embodiment of the tetracarboxylic acid derivative, it is particularly preferred that the tetracarboxylic acid derivative contains a compound selected from the group consisting of compounds represented by the following formulae (X1-1-1) to (X1-1-6),

[0166]

[0167] At least one compound (T) selected from the group consisting of the compounds represented by the above formulae (X1-6) to (X1-9), 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,4,5-pyromellitic anhydride, the compound represented by (Xb-6), and their tetracarboxylic acid diesters and tetracarboxylic acid diester dichlorides.

[0168] The amount of these preferred compounds (T) used (the total amount when two or more are used) is preferably 10 mol% or more, more preferably 20 mol% or more, and further preferably 30 mol% or more, relative to the total amount of tetracarboxylic dianhydride and its derivatives used in the synthesis of the polyamic acid.

[0169] The molecular weight of the polyamic acid, polyamic acid ester and polyimide of the present invention is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, further preferably 10,000 to 100,000, and the number average molecular weight is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, further preferably 5,000 to 50,000.

[0170] <<(A) Quantity of ingredient>>

[0171] When the total amount of the liquid crystal aligning agent is 100% by weight, (A) component is 1 to 15% by weight, preferably 1 to 8% by weight, more preferably 1.5 to 7% by weight.

[0172] <(B) Component>

[0173] The liquid crystal aligning agent of the present application contains the (B) component.

[0174] (B) Component is at least one compound selected from the group consisting of a compound represented by the following formula [CL-1] and a compound represented by the following formula [CL-2].

[0175] By containing these compounds, when a liquid crystal aligning film is formed from a liquid crystal aligning agent, the adhesion between the liquid crystal aligning film and a substrate and / or the adhesion between the liquid crystal aligning film and a member provided thereon can be improved.

[0176]

[0177] (CL-1) In the formula, r 1represents a hydrogen atom or a methyl group;

[0178] r 2 represents an alkylene group having 2 to 20 carbon atoms, more preferably an alkylene group having 2 to 10 carbon atoms, a divalent organic group consisting of an aliphatic ring having 5 to 6 carbon atoms, or a divalent aliphatic group containing an aliphatic ring having 5 to 6 carbon atoms, wherein -CH 2 - is optionally replaced by -O-;

[0179] r 3 represents a k-valent aliphatic group having 2 to 20 carbon atoms, a k-valent linear or branched alkylene group having 2 to 20 carbon atoms, a k-valent group formed by an aliphatic ring having 5 to 6 carbon atoms, or a k-valent aliphatic group containing an aliphatic ring having 5 to 6 carbon atoms, wherein -CH 2 - is optionally substituted with -O-, more preferably represents a k-valent aliphatic group having 2 to 10 carbon atoms, more preferably represents a k-valent alkyl group having 2 to 10 carbon atoms;

[0180] Z represents a divalent group represented by the above formula (1a),

[0181] k is a natural number of 2 to 9, and is preferably a natural number of 2 to 6.

[0182] It should be noted that in formula (1a),

[0183] r 4 represents an alkyl group having 1 to 20 carbon atoms, preferably an alkyl group having 1 to 10 carbon atoms, more preferably a linear or branched alkyl group having 1 to 6 carbon atoms, a monovalent group formed by an aliphatic ring having 5 to 6 carbon atoms, or a monovalent aliphatic group containing an aliphatic ring having 5 to 6 carbon atoms, wherein -CH 2 - is optionally replaced by -O-, preferably methyl.

[0184] In *1 and *2, one represents a bond to a nitrogen atom, and the other represents a bond to r 3 connection key.

[0185] As r 2 Specific examples of the alkylene group having 2 to 20 carbon atoms in the definition include a divalent group obtained by further removing one hydrogen atom from an alkyl group having 2 to 20 carbon atoms.

[0186] Specific examples of the alkyl group having 2 to 20 carbon atoms include, for example, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, n-octadecyl, n-nonadecyl, n-eicosyl, cyclopentyl, cyclohexyl, and groups in which one or more of these groups are bonded to each other within a range of up to 20 carbon atoms; and groups in which one or more non-adjacent methylene groups of these groups are replaced with ether bonds.

[0187] As r 2 The monovalent group formed by an aliphatic ring having 5 to 6 carbon atoms in the definition includes, for example, cyclopentyl and cyclohexyl;

[0188] As r 2 Examples of the monovalent aliphatic group containing an aliphatic ring having 5 to 6 carbon atoms in the definition include an alkyl group containing a cyclopentyl ring or a cyclohexane ring.

[0189] As r 3 Specific examples of the k-valent aliphatic group having 2 to 20 carbon atoms in the definition of include k-valent groups obtained by further removing 1 to (k-1) hydrogen atoms from an alkyl group having 2 to 20 carbon atoms. It should be noted that the alkyl group having 2 to 20 carbon atoms has the same definition as that of R2 above.

[0190] As r 3 Examples of the k-valent group formed by an aliphatic ring having 5 to 6 carbon atoms in the definition include a k-valent group formed by removing k hydrogen atoms from a cyclopentyl ring or a cyclohexane ring.

[0191] In addition, as r 3 Examples of the k-valent aliphatic group containing an aliphatic ring having 5 to 6 carbon atoms in the definition include a k-valent alkyl group containing a cyclopentyl ring or a cyclohexane ring.

[0192] As r 2 With r 3 From the perspective of raw material availability, r 2 is ethylene, r 3 It is n-hexylidene.

[0193] As r 4 In the definition of alkyl with 1 to 20 carbon atoms, except for r 2The alkyl group with 2 to 20 carbon atoms in the definition may also include methyl,

[0194] As r 4 The monovalent group formed by an aliphatic ring having 5 to 6 carbon atoms in the definition includes, for example, cyclopentyl and cyclohexyl;

[0195] In addition, as r 4 Examples of the monovalent aliphatic group containing an aliphatic ring having 5 to 6 carbon atoms in the definition include an alkyl group containing a cyclopentyl ring or a cyclohexane ring.

[0196] (CL-2) In the formula, R CL1 is a hydrogen atom or a methyl group,

[0197] R CL2 and R CL3 are independently a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or a hydroxyalkyl group having 1 to 20 carbon atoms, preferably an alkyl group having 1 to 10 carbon atoms or a hydroxyalkyl group having 1 to 20 carbon atoms, more preferably a linear or branched alkyl group having 1 to 10 carbon atoms or a linear or branched hydroxyalkyl group having 1 to 20 carbon atoms,

[0198] R CL4 It is a hydroxyl group or a hydroxyalkyl group having 1 to 20 carbon atoms, preferably a hydroxyl group or a hydroxyalkyl group having 1 to 10 carbon atoms, and more preferably a hydroxyl group or a linear or branched hydroxyalkyl group having 1 to 6 carbon atoms.

[0199] As R CL2 , R CL3 Specific examples of the alkyl group having 1 to 20 carbon atoms in the alkyl group include, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, n-octadecyl, n-nonadecyl, and n-eicosyl.

[0200] It should be noted that n, i, s, and t represent normal, iso, secondary, and tertiary, respectively.

[0201] As R CL2 , R CL3Specific examples of the hydroxyalkyl group having 1 to 20 carbon atoms, preferably a group in which a hydroxy group is substituted at the terminal of the alkyl group, include, for example, a hydroxymethyl group, a 2-hydroxyethyl group, a 3-hydroxypropyl group, a 4-hydroxybutyl group, a 5-hydroxypentyl group, a 6-hydroxyhexyl group, a 7-hydroxyheptyl group, an 8-hydroxyoctyl group, a 9-hydroxynonyl group, a 10-hydroxydecyl group, a 11-hydroxyundecyl group, a 12-hydroxydodecyl group, a 13-hydroxytridecyl group, a 14-hydroxytetradecyl group, a 15-hydroxypentadecyl group, a 16-hydroxyhexadecyl group, a 17-hydroxyheptadecyl group, a 18-hydroxyoctadecyl group, a 19-hydroxynonadecyl group, and a 20-hydroxyeicosyl group.

[0202] Examples of the compound represented by the formula (CL-1) include the following (MA-M1) to (MA-M3), but the compound is not limited to these.

[0203]

[0204] Among the compounds listed above, (MA-M1) and (MA-M3) are preferred, and (MA-M1) is more preferred.

[0205] Examples of the compound represented by the formula (CL-2) include the following (G-M1) to (G-M4), but the compound is not limited to these.

[0206]

[0207] Among the compounds listed above, (G-M1), (G-M2), and (G-M4) are preferred, and (G-M1) is more preferred.

[0208] <<(B) Quantity of component>>

[0209] In the liquid crystal aligning agent of the present application, the component (B) is contained in an amount of 0.1 to 50 parts by weight, preferably 0.1 to 30 parts by weight, and more preferably 0.1 to 20 parts by weight, relative to 100 parts by weight of the component (A).

[0210] <Component (C): Organic Solvent>

[0211] The liquid crystal aligning agent of the present application contains an organic solvent as (C) component.

[0212] The organic solvent is not particularly limited as long as it has the property of dissolving the above-mentioned components (A) and (B).

[0213] Any organic solvent is preferred as long as it is suitable for the low-temperature calcination process.

[0214] Examples of the organic solvent of the component (C) of the present application include, but are not limited to, the following solvents belonging to Groups A and B. In addition, these solvents may be used alone or in combination.

[0215] <Group A>

[0216] For solvents belonging to Group A, when it is desired to improve the solubility of the above-mentioned polyimides, polyamic acids, polyamic acid esters, polyorganosiloxanes, polyesters, polyamides, and polymers of monomers having polymerizable unsaturated bonds, etc., it is preferable to use the solvents shown below (also referred to as Group A).

[0217] For example, at least one solvent selected from the group consisting of N-methyl-2-pyrrolidone, the compound represented by the following formula (NP), the compound represented by the following (NAm), γ-butyrolactone, γ-valerolactone, and 1,3-dimethyl-2-imidazolidinone.

[0218]

[0219] In formula (NP), R 1 is a monovalent hydrocarbon group having 2 to 5 carbon atoms, or a monovalent group having "-O-" between carbon-carbon bonds in the hydrocarbon group. In formula (NAm), R2 and R3 are each independently a hydrogen atom, a monovalent hydrocarbon group having 1 to 6 carbon atoms, or a monovalent group having "-O-" between carbon-carbon bonds in the hydrocarbon group, and R2 and R3 may optionally be bonded to each other to form a ring structure. R4 is an alkyl group having 1 to 6 carbon atoms.), and these solvents are solvents that dissolve the polymer in the liquid crystal aligning agent.

[0220] Specific examples of the compound represented by the above formula (NP) include, for example: N-ethyl-2-pyrrolidone, N-(n-propyl)-2-pyrrolidone, N-isopropyl-2-pyrrolidone, N-(n-butyl)-2-pyrrolidone, N-(tert-butyl)-2-pyrrolidone, N-(n-pentyl)-2-pyrrolidone, N-methoxypropyl-2-pyrrolidone, N-ethoxyethyl-2-pyrrolidone, N-methoxybutyl-2-pyrrolidone, etc.

[0221] Specific examples of the compound represented by the above formula (NAm) include, for example: 3-butoxy-N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-hexyloxy-N,N-dimethylpropanamide, isopropoxy-N-isopropyl-propanamide, n-butoxy-N-isopropyl-propanamide, etc.

[0222] In the solvent A group, it is preferably at least one compound selected from the group consisting of N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, 3-butoxy-N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-hexyloxy-N,N-dimethylpropanamide, isopropoxy-N-isopropyl-propionamide, and n-butoxy-N-isopropyl-propionamide, and more preferably at least one compound selected from the group consisting of N-methyl-2-pyrrolidone, γ-butyrolactone, and 1,3-dimethyl-2-imidazolidinone.

[0223] <Group B>

[0224] From the perspective of improving the coatability of the liquid crystal aligning agent on the substrate and increasing the drying rate of the liquid crystal aligning agent even during low-temperature firing, the liquid crystal aligning agent of the present invention preferably contains at least one compound selected from the group consisting of the compound represented by the following formula (Sol-1), the following formula (Sol-2), the solvent represented by the following formula (a), methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, 1-butanol, tert-butanol, 1-pentanol, 2-methyl-1-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-ethyl-1-butanol, 1-heptanol, 1-octanol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, dipropyl ether, dibutyl ether, dihexyl ether, dioxane, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 1-methylpentyl acetate, 2-ethylhexyl acetate, propylene carbonate, ethylene carbonate, furfuryl alcohol, methyl acetate, ethyl acetate, n-butyl acetate, methyl pyruvate, ethyl pyruvate, and diisobutyl ketone (hereinafter referred to as Group B). It preferably contains at least one compound selected from the group consisting of the compound represented by the following formula (Sol-1) and the compound represented by the following formula (Sol-2).

[0225]

[0226] In formula (Sol-1),

[0227] Y s 7 and Y s 8 are each independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms, and preferably include a monovalent chain hydrocarbon group having 1 to 6 carbon atoms, a monovalent alicyclic hydrocarbon group having 1 to 6 carbon atoms, and a monovalent aromatic hydrocarbon group having 1 to 6 carbon atoms, etc. More preferably, it is an alkyl group having 1 to 6 carbon atoms.

[0228] X s 1 is an oxygen atom or -COO-.

[0229] X s 2 is a single bond or a carbonyl group,

[0230] R s 7 is an alkanediyl group having 2 to 4 carbon atoms, R s 7 The alkanediyl group may be linear or branched, and examples thereof include methylene, ethylene, 1,3-propylene, 1,2-propylene, 1,4-butanediyl, and 1,3-butanediyl. s 7 Preferred is ethylene, 1,3-propylene or 1,4-butanediyl.

[0231] n s 1 is an integer from 1 to 3, n s 1 When it is 2 or 3, multiple R s 7 They may be the same or different, and are preferably 1 or 2.

[0232] In formula (Sol-2),

[0233] Z s 1 It is a divalent hydrocarbon group having 1 to 6 carbon atoms, preferably an alkanediyl group, and examples thereof include a methylene group, an ethylene group, a 1,3-propylenediyl group, and a 1,4-butylenediyl group.

[0234] Y s 9 and Y s 10 Each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms, and preferably includes a monovalent chain hydrocarbon group having 1 to 6 carbon atoms, a monovalent alicyclic hydrocarbon group having 1 to 6 carbon atoms, and a monovalent aromatic hydrocarbon group having 1 to 6 carbon atoms.

[0235] More preferably, it is an alkyl group having 1 to 6 carbon atoms.

[0236]

[0237] In the formula, R 1 , R 2 are each independently a linear or branched alkyl group having 1 to 8 carbon atoms. 1 +R 2 is an integer greater than 3.

[0238] In Group B, preferably selected from the compounds represented by the above formula (Sol-1), the above formula (Sol-2), the solvent represented by the above formula (a), methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, 1-butanol, tert-butanol, 1-pentanol, 2-methyl-1-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-ethyl-1-butanol, 1-heptanol, 1-octanol, 2-ethyl-1-hexanol at least one compound selected from the group consisting of alcohol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, dipropyl ether, dibutyl ether, dihexyl ether, dioxane, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 1-methylpentyl acetate, 2-ethylhexyl acetate, propylene carbonate, ethylene carbonate, furfuryl alcohol, n-butyl acetate, methyl pyruvate, ethyl pyruvate, and diisobutyl ketone,

[0239] More preferably, it is at least one compound selected from the group consisting of the compound represented by the above formula (Sol-1), the above formula (Sol-2), the above formula (a), methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, dipropyl ether, dibutyl ether, dihexyl ether, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 1-methylpentyl acetate, 2-ethylhexyl acetate, propylene carbonate, ethylene carbonate, and diisobutyl ketone. Most preferably, it is at least one compound selected from the group consisting of the compound represented by the above formula (Sol-1) and the compound represented by the above formula (Sol-2).

[0240] Specific examples of the solvent represented by formula (Sol-1) include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol-n-propyl ether, ethylene glycol-isopropyl ether, ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol monohexyl ether, ethylene glycol dimethyl ether, ethylene glycol monoacetate, ethylene glycol diacetate, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monobutyl ether, dipropylene glycol dimethyl ether, dipropylene glycol monomethyl ether, propylene glycol diacetate, ethylene glycol, 1,4-butanediol, 3-ethoxybutyl acetate, etc.

[0241] Specific examples of the solvent represented by (Sol-2) include methyl glycolate, ethyl glycolate, butyl glycolate, ethyl lactate, butyl lactate, isoamyl lactate, ethyl 3-ethoxypropionate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid ester, 3-methoxypropionic acid ester, propyl 3-methoxypropionic acid, and butyl 3-methoxypropionic acid.

[0242] Preferred specific examples of formula (Sol-1) to (Sol-2) include: ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol-n-propyl ether, ethylene glycol-isopropyl ether, ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, propylene glycol monobutyl ether, dipropylene glycol dimethyl ether, dipropylene glycol monomethyl ether, propylene glycol diacetate, ethyl 3-ethoxypropionate, and methyl 3-methoxypropionate.

[0243] As a preferable solvent of the above formula (a), diisobutyl methanol can be mentioned.

[0244] In the liquid crystal alignment agent of the present invention, it is preferred to use group A and group B together, in which case group B is preferably 5 to 95% by mass or less of the total solvent contained in the liquid crystal alignment agent, more preferably 5 to 80% by mass or less, and further preferably 30 to 80% by mass or less. In addition, group A is preferably 5 to 95% by mass or less of the total solvent contained in the liquid crystal alignment agent, more preferably 20 to 95% by mass, and further preferably 20 to 70% by mass or less.

[0245] <<Components other than component (A) to component (C)>>

[0246] The liquid crystal aligning agent of the present application may contain any component other than the above-mentioned (A) component to (C) component as appropriate.

[0247] <Other cross-linking compounds>

[0248] As components other than components (A) to (C), in addition to the compounds having an epoxy group, an isocyanate group, an oxetane group or a cyclocarbonate group, or a compound having at least one group selected from the group consisting of a hydroxyl group, a hydroxyalkyl group and a lower alkoxyalkyl group, which are described in paragraphs

[0109] to

[0113] of International Publication WO2016 / 047771, compounds having a blocked isocyanate group (these are collectively referred to as other cross-linking compounds) can also be used.

[0249] Examples of the compound having a blocked isocyanate group include the following formulae (bl-1) to (bl-3).

[0250]

[0251] The above is an example of other crosslinking compounds, and the invention is not limited to these compounds. In addition, other crosslinking compounds used in the liquid crystal aligning agent of the present invention may be used alone or in combination of two or more.

[0252] In the liquid crystal aligning agent of the present invention, the content of other crosslinking compounds is preferably 0.1 to 150 parts by mass relative to 100 parts by mass of all polymer components. In order to allow the crosslinking reaction to proceed and exert the target effect, the content is preferably 0.1 to 100 parts by mass relative to 100 parts by mass of the polymer components. More preferably, it is 1 to 50 parts by mass.

[0253] <Other optional ingredients>

[0254] In the liquid crystal aligning agent of the present invention, a compound that improves the uniformity of the film thickness and the surface smoothness of the liquid crystal aligning film when the liquid crystal aligning agent is applied can be used.

[0255] As compounds for improving the uniformity of the film thickness and the surface smoothness of the liquid crystal alignment film, fluorine-based surfactants, silicone-based surfactants, nonionic surfactants, etc. can be cited. For these specific examples, the surfactants described in paragraph

[0117] of the International Publication WO2016 / 047771 can be cited. The amount of the surfactant is preferably 0.01 to 2 parts by mass, more preferably 0.01 to 1 part by mass, relative to 100 parts by mass of all polymer components contained in the liquid crystal alignment agent.

[0256] Furthermore, a nitrogen-containing heterocyclic amine compound represented by formula [M1] to [M156], which is recorded on pages 69 to 73 of International Publication WO2011 / 132751 (published on October 27, 2011), can be added to the liquid crystal alignment agent as a compound that promotes charge transfer in the liquid crystal alignment film to promote the decharge of the element. The amine compound can be directly added to the liquid crystal alignment agent, but is preferably added after making a solution with a concentration of 0.1 to 10% by mass, preferably 1 to 7% by mass. The solvent is not particularly limited as long as it dissolves the specific polymer (A).

[0257] In addition to the above-mentioned poor solvents, cross-linking compounds, compounds that improve the uniformity of the film thickness of the resin film or the liquid crystal orientation film, the surface smoothness, and the compounds that promote decharge, a silane coupling agent may be added to the liquid crystal orientation agent of the present invention to improve the adhesion between the polymer other than the polymer described in the present invention, the orientation film and the substrate, and further, an imidization promoter may be added to effectively carry out imidization by heating the polyimide precursor when the coating is fired.

[0258] The liquid crystal aligning agent of the present application has a solution form containing the above-mentioned (A) component to (C) component.

[0259] The liquid crystal aligning agent used for this invention has the solution form which melt|dissolved the polymer of a specific structure in the organic solvent.

[0260] The concentration of the polymer used in the liquid crystal alignment agent of the present invention can be appropriately changed according to the setting of the thickness of the formed coating film, but from the perspective of forming a uniform and defect-free coating film, it is preferably 1 weight % or more, and from the perspective of the storage stability of the solution, it is preferably set to 10 weight % or less.

[0261] For the liquid crystal alignment agent of the present application, the solid content concentration (the ratio of the total weight of the components other than the component (C) of the liquid crystal alignment agent to the total weight of the liquid crystal alignment agent) can be appropriately changed according to the setting of the thickness of the formed coating film, but from the perspective of forming a uniform and defect-free coating film, it is preferably 1 weight % or more, and from the perspective of the storage stability of the solution, it is preferably set to 10 weight % or less.

[0262] The particularly preferred range of the solid content concentration varies depending on the method of applying the liquid crystal aligning agent to the substrate.

[0263] For example, when a spin coating method is used, the polymer concentration is preferably in the range of 1.5 to 4.5 wt%. When a printing method is used, it is particularly preferred to set the solid content concentration in the range of 3 to 9 wt%, thereby setting the solution viscosity in the range of 12 to 50 mPa·s. When an inkjet method is used, it is particularly preferred to set the solid content concentration in the range of 1 to 5 wt%, thereby setting the solution viscosity in the range of 3 to 15 mPa·s.

[0264] According to another aspect of the present invention, a liquid crystal aligning film formed using the liquid crystal aligning agent of the present invention is provided.

[0265] In addition, according to another embodiment of the present invention, a method for manufacturing a liquid crystal alignment film is provided, the method comprising: a process of coating the liquid crystal alignment agent of the present invention on a substrate to form a coating film; and a process of irradiating the coating film with light when the coating film is not in contact with the liquid crystal layer or when the coating film is in contact with the liquid crystal layer.

[0266] Furthermore, according to another aspect of the present invention, there is provided a liquid crystal display element including the liquid crystal aligning film of the present invention or the liquid crystal aligning film obtained by the manufacturing method of the present invention.

[0267] <Liquid crystal alignment film and liquid crystal display element>

[0268] By using the above-mentioned liquid crystal alignment agent, a liquid crystal alignment film can be manufactured. In addition, the liquid crystal display element of the present invention has a liquid crystal alignment film formed by using the above-mentioned liquid crystal alignment agent. There is no particular restriction on the operation mode of the liquid crystal display element of the present invention, for example, it can be applied to various operation modes such as TN (Twisted Nematic) type, STN type, vertical alignment type (including VA-MVA type, VA-PVA type, etc.), in-plane switching type (IPS type), FFS (Fringe Field Switching) type, optical compensation bending type (OCB type), etc.

[0269] The liquid crystal display element of the present invention can be produced, for example, by a process including the following steps (1-1) to (1-3). In step (1-1), the substrate used varies depending on the desired operation mode. In steps (1-2) and (1-3), each operation mode is common.

[0270] [Step (1-1): Forming a coating film]

[0271] First, the liquid crystal aligning agent of the present invention is applied on a substrate, and then the applied surface is heated to form a coating film on the substrate.

[0272] (1-1A) For example, when manufacturing a TN type, STN type or VA type liquid crystal display element, first, two substrates provided with patterned transparent conductive films are used as a pair, and the liquid crystal alignment agent prepared above is preferably applied to each transparent conductive film forming surface thereof by offset printing, spin coating, roller coating or inkjet printing. As the substrate, for example, glass such as float glass and soda glass can be used; transparent substrates made of plastics such as polyethylene terephthalate, polybutylene terephthalate, polyether sulfone, polycarbonate, poly(alicyclic olefin) and the like can be used. As a transparent conductive film provided on one surface of the substrate, a substrate made of tin oxide (SnO 2 ) made of NESA film (a registered trademark of PPG, USA), indium oxide-tin oxide (In 2 O 3 -SnO 2 ) and the like. In order to obtain a patterned transparent conductive film, for example, the following methods can be used: a method of forming a pattern by photolithography after forming a non-patterned transparent conductive film; a method of using a mask with a desired pattern when forming a transparent conductive film, etc. When applying a liquid crystal alignment agent, in order to further improve the adhesion between the substrate surface and the transparent conductive film and the coating film, a pretreatment can be performed, and a functional silane compound, a functional titanium compound, etc. can be pre-coated on the surface of the substrate surface where the coating film is formed.

[0273] After applying the liquid crystal alignment agent, in order to prevent the applied liquid crystal alignment agent from dripping, etc., preheating (prebaking) is preferably performed. The prebaking temperature is preferably 30 to 200°C, more preferably 40 to 150°C, and particularly preferably 40 to 100°C. The prebaking time is preferably 0.25 to 10 minutes, and more preferably 0.5 to 5 minutes. Thereafter, a calcination (post-baking) process is performed, the purpose of which is to completely remove the solvent and thermally imidize the amide acid structure present in the polymer as needed. The calcination temperature (post-baking temperature) at this time is preferably 80 to 300°C, and more preferably 120 to 250°C. The post-baking time is preferably 5 to 200 minutes, and more preferably 10 to 100 minutes. The film thickness of the film formed in this way is preferably 0.001 to 1 μm, and more preferably 0.005 to 0.5 μm.

[0274] (1-1B) When manufacturing an IPS type or FFS type liquid crystal display element, a liquid crystal alignment agent is applied to the electrode-forming surface of a substrate provided with an electrode made of a comb-shaped patterned transparent conductive film or metal film, and to one surface of an opposing substrate without an electrode, and then a coating film is formed by heating each coated surface. The material of the substrate and transparent conductive film used at this time, the coating method, the heating conditions after coating, the patterning method of the transparent conductive film or metal film, the pretreatment of the substrate, and the preferred film thickness of the formed coating film are the same as those in (1-1A) above. As a metal film, for example, a film formed of a metal such as chromium can be used.

[0275] In any of the above (1-1A) and (1-1B), after the liquid crystal alignment agent is applied to the substrate, the organic solvent is removed to form a liquid crystal alignment film or a coating film serving as the liquid crystal alignment film. At this time, after the coating film is formed, the polyamic acid, polyamic acid ester and polyimide blended in the liquid crystal alignment agent of the present invention can be further heated to undergo a dehydration ring-closure reaction to prepare a further imidized coating film.

[0276] [Step (1-2): Treatment for imparting orientation ability]

[0277] When manufacturing TN type, STN type, IPS type or FFS type liquid crystal display elements, the coating formed in the above step (1-1) is subjected to a treatment of imparting liquid crystal orientation ability. As a result, the coating is endowed with the orientation ability of liquid crystal molecules to become a liquid crystal orientation film. As a treatment for imparting orientation ability, for example, there can be cited: a cloth made of fibers such as nylon, rayon, cotton, etc. is wound on a roller, and a brushing treatment of rubbing the coating in a certain direction with the roller; a light orientation treatment of irradiating polarized light or non-polarized light radiation to the coating. On the other hand, when manufacturing a VA type liquid crystal display element, the coating formed in the above step (1-1) can be used directly as a liquid crystal orientation film, or the coating can be subjected to a treatment of imparting orientation ability.

[0278] When the coating film is given liquid crystal orientation ability by photo-orientation treatment, as the radiation irradiating the coating film, for example, ultraviolet rays and visible light containing light with a wavelength of 150 to 800 nm can be used. When the radiation is polarized light, it can be linear polarized light or partially polarized light. In addition, when the radiation used is linear polarized light or partially polarized light, it can be irradiated from a direction perpendicular to the substrate surface, it can also be irradiated from an oblique direction, or it can be irradiated in combination. In the case of irradiating non-polarized radiation, the irradiation direction is set to an oblique direction.

[0279] As the light source used, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. Ultraviolet rays in a preferred wavelength range can be obtained by using a light source together with, for example, a filter, a diffraction grating, etc. The irradiation amount of the radiation is preferably 10 to 5,000 mJ / cm 2 , more preferably 30 to 2,000 mJ / cm 2 .

[0280] In order to improve the reactivity, the coating film may be irradiated with light while being heated. The temperature during heating is usually 30 to 250°C, preferably 40 to 200°C, and more preferably 50 to 150°C.

[0281] In addition, when ultraviolet rays containing light with a wavelength of 150 to 800 nm are used, the light irradiation film obtained in the above process can be used directly as a liquid crystal alignment film, but the light irradiation film can also be fired. The firing temperature at this time is preferably 80 to 300°C, more preferably 120 to 250°C. The firing time is preferably 5 to 200 minutes, more preferably 10 to 100 minutes. The photo-alignment treatment here is equivalent to the light irradiation treatment in a state where it is not in contact with the liquid crystal layer.

[0282] It should be noted that the following treatments may also be performed: by further irradiating the liquid crystal alignment film after the brushing treatment with ultraviolet rays, thereby changing the pretilt angle of a part of the liquid crystal alignment film; or forming a resist film on a part of the surface of the liquid crystal alignment film, and then performing a brushing treatment in a direction different from the previous brushing treatment, and then removing the resist film, so that the liquid crystal alignment film has different liquid crystal alignment capabilities in each region. In this case, the viewing characteristics of the resulting liquid crystal display element can be improved. The liquid crystal alignment film suitable for VA type liquid crystal display elements can also be suitable for PSA (Polymer sustained alignment) type liquid crystal display elements.

[0283] [Step (1-3): Construction of Liquid Crystal Cell]

[0284] (1-3A) As described above, two substrates formed with liquid crystal alignment films are prepared, and a liquid crystal cell is manufactured by arranging a liquid crystal between the two substrates arranged oppositely. For example, the following two methods can be cited to manufacture a liquid crystal cell. The first method is a method known in the past. First, two substrates are arranged oppositely with a gap (cell gap) between them, so that each liquid crystal alignment film is opposite to each other, and the peripheral portions of the two substrates are bonded with a sealant. The liquid crystal is injected and filled into the cell gap divided by the substrate surface and the sealant, and then the liquid crystal cell is manufactured by sealing the injection hole. The second method is a method called ODF (One Drop Fill) method. At a specified position on one of the two substrates formed with a liquid crystal alignment film, a UV-curable sealant is applied, for example, and then liquid crystals are dropped on several specified positions on the surface of the liquid crystal alignment film, and then another substrate is pasted so that the liquid crystal alignment films are opposite to each other, and the liquid crystal is spread on the entire surface of the substrate, and then the sealant is cured by irradiating ultraviolet light to the entire surface of the substrate, thereby manufacturing a liquid crystal cell. When any of the methods is used, it is desirable that the liquid crystal cell manufactured as described above is further heated to a temperature at which the liquid crystal used is in an isotropic phase, and then gradually cooled to room temperature to remove the flow orientation when the liquid crystal is filled.

[0285] As the sealant, for example, epoxy resin containing a hardener and alumina balls as spacers can be used.

[0286] As liquid crystal, nematic liquid crystal and smectic liquid crystal can be listed, among which nematic liquid crystal is preferred, for example, Schiff base liquid crystal, azo oxygen liquid crystal, biphenyl liquid crystal, phenylcyclohexane liquid crystal, ester liquid crystal, terphenyl liquid crystal, biphenylcyclohexane liquid crystal, pyrimidine liquid crystal, dioxane liquid crystal, bicyclooctane liquid crystal, cubane liquid crystal, etc. can be used. In addition, cholesteric liquid crystals such as cholestyramine chloride, cholesteryl nonyl ester, and cholesteryl carbonate can be added to these liquid crystals; chiral agents sold under the trade names "C-15" and "CB-15" (Merck Company); ferroelectric liquid crystals such as p-decyloxybenzylidene-p-amino-2-methylbutylcinnamate can be used. The liquid crystal can also contain anisotropic dyes. The term "dye" may refer to a substance that can absorb or change light in a concentrated manner in the visible light region, for example, at least a portion or the entire range of the wavelength range of 400nm to 700nm; the term "anisotropic dye" may refer to a substance that can anisotropically absorb light in at least a portion or the entire range of the visible light region. As described above, the color sense of the liquid crystal unit can be adjusted by using a dye. There is no particular restriction on the type of anisotropic dye, for example, a black dye or a color dye can be used. For the ratio of anisotropic dye to liquid crystal, it is appropriately selected within the range that does not damage the target physical properties. For example, the anisotropic dye can be contained in a ratio of 0.01 to 5 parts by weight relative to 100 parts by weight of the liquid crystal compound, but the ratio can be changed to an appropriate range as needed.

[0287] (1-3B) When manufacturing a PSA type liquid crystal display element, a liquid crystal unit is constructed in the same manner as in (1-3A) above, except that a photopolymerizable compound is injected or dripped together with the liquid crystal. Thereafter, the liquid crystal unit is irradiated with light while a voltage is applied between the conductive films of a pair of substrates. The voltage applied here can be set to, for example, a direct current or alternating current of 5 to 50 V. In addition, as the irradiated light, for example, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm can be used, but ultraviolet light containing light with a wavelength of 300 to 400 nm is preferred. As a light source for the irradiated light, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. It should be noted that the ultraviolet light in the preferred wavelength region can be obtained by using a light source together with, for example, a filter, a diffraction grating, etc. As the irradiation amount of light, 100 mJ / cm 2 Above and less than 20,000mJ / cm 2 , more preferably 100 to 10,000 mJ / cm 2 .

[0288] (1-3C) When a coating film is formed on a substrate using a compound (polymer or additive) containing a photopolymerizable group, the following method can also be used: a liquid crystal unit is constructed in the same manner as in the above (1-3A), and then, a liquid crystal display element is manufactured by irradiating the liquid crystal unit with light while a voltage is applied between the conductive films of a pair of substrates. According to this method, there is an advantage of being able to achieve a PSA mode with a smaller amount of light irradiation. The light irradiation of the liquid crystal unit can be performed in a state where the liquid crystal is driven by applying a voltage, or it can be performed without driving the liquid crystal while applying a low voltage. The applied voltage can be set to, for example, a direct current or alternating current of 0.1 to 30 V. For the conditions of the irradiated light, the description of (1-3B) above can be used. The light irradiation treatment here is equivalent to the light irradiation treatment in a state of contact with the liquid crystal layer.

[0289] Then, by attaching a polarizing plate to the outer surface of the liquid crystal cell, the liquid crystal display element of the present invention can be obtained. As the polarizing plate attached to the outer surface of the liquid crystal cell, there can be cited a polarizing plate formed by sandwiching a polarizing film between cellulose acetate protective films, wherein the polarizing film is a polarizing film called "H film" formed by stretching and orienting polyvinyl alcohol while absorbing iodine; or a polarizing plate made of the H film itself.

[0290] The liquid crystal display element of the present invention can be effectively applied to various devices, for example, it can be used in various display devices such as clocks, portable game consoles, word processors, notebook computers, car navigation systems, camcorders, PDAs, digital cameras, mobile phones, smartphones, various monitors, liquid crystal televisions and information displays.

[0291] As described above, by using the liquid crystal aligning agent of the present invention, a liquid crystal aligning film having good adhesion can be obtained even when low-temperature baking is performed.

[0292] Example

[0293] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited thereto. The abbreviations of the compounds used are as follows.

[0294] (liquid crystal)

[0295] LC-V1: MLC-6608 (Merck)

[0296] LC-I1: MLC-2041 (Merck)

[0297] LC-I2: MLC-7026-100 (Merck)

[0298] (Diamine component)

[0299] A1: 1,3-Diamino-4-[4-(trans-4-n-heptylcyclohexyl)phenoxy]benzene

[0300] A2: 1,3-Diamino-4-[4-(trans-4-n-heptylcyclohexyl)phenoxymethyl]benzene

[0301] A3: 1,3-Diamino-4-{4-[trans-4-(trans-4-n-pentylcyclohexyl)cyclohexyl]phenoxy}benzene

[0302] A4: diamine compound represented by formula [A4]

[0303] A5: 1,3-Diamino-4-octadecyloxybenzene

[0304] A6: 1,3-Diamino-4-hexadecyloxybenzene

[0305] A8: N-(2,4-diaminophenyl)-4-(trans-4-heptylcyclohexyl)benzamide (compound represented by formula [A8])

[0306]

[0307] B1: 3,5-diaminobenzoic acid

[0308] B2: 2,4-diamino-N,N-diallylaniline (a diamine compound represented by the following formula [B2])

[0309]

[0310] C1: p-phenylenediamine

[0311] C2: m-phenylenediamine

[0312] C3: 1,5-bis(4-aminophenoxy)pentane

[0313] C4: 1,3-bis(4-aminophenethyl)urea

[0314] C5: 4-(2-(methylamino)ethyl)aniline (compound represented by formula [C5])

[0315] C6: Compound represented by formula [C6]

[0316] C7: 1,2-bis(4-aminophenoxy)ethane

[0317] C8: 4,4'-diaminodiphenylmethane

[0318] DA-N-A6: 4,4'-Diaminodiphenylamine

[0319] DA-N-A7: Bis(4-aminophenyl)-N-methylamine

[0320]

[0321] (Tetracarboxylic acid component)

[0322] D1: 1,2,3,4-cyclobutanetetracarboxylic dianhydride

[0323] D2: Bicyclo[3,3,0]octane-2,4,6,8-tetracarboxylic dianhydride

[0324] D3: Tetracarboxylic dianhydride represented by formula [D3]

[0325] D4: Tetracarboxylic dianhydride represented by formula [D4]

[0326] D5: Tetracarboxylic dianhydride represented by formula [D5]

[0327] D6: 1,2,3,4-Butanetetracarboxylic dianhydride

[0328] D7: 1,2,4,5-pyromellitic anhydride

[0329] D8: 3,3',4,4'-biphenyltetracarboxylic dianhydride

[0330] D9: 2,4-bis(methoxycarbonyl)cyclobutane-1,3-dicarboxylic acid (compound represented by formula [D9]) D10: 2,5-bis(methoxycarbonyl)benzene-1,4-dicarboxylic acid (compound represented by formula

[10] )

[0331]

[0332] (Condensation agent)

[0333] DMT-MM: 4-(4,6-dimethoxy-1,3,5-triazine-2-yl)-4-methylmorpholinium (adhesive compound)

[0334] G-M1: Adhesive compound represented by formula [G-M1]

[0335] MA-M1: Adhesive compound represented by formula [MA-M1]

[0336]

[0337] (Other adhesive compounds)

[0338] K1: Compound represented by formula [K1]

[0339]

[0340] K2: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd.)

[0341] (Solvent)

[0342] NMP: N-methyl-2-pyrrolidone

[0343] NEP: N-ethyl-2-pyrrolidone

[0344] γ-BL: γ-butyrolactone

[0345] DMI: 1,3-dimethyl-2-imidazolidinone

[0346] PGME: Propylene glycol monomethyl ether

[0347] ECS: Ethylene glycol monoethyl ether

[0348] BCS: Ethylene glycol monobutyl ether

[0349] PB: Propylene glycol monobutyl ether

[0350] EC: Diethylene glycol monoethyl ether

[0351] EEP: Ethyl 3-ethoxypropionate

[0352] DEDE: Diethylene glycol diethyl ether

[0353] DME: Dipropylene glycol dimethyl ether

[0354] DEME: Diethylene glycol dimethyl ether

[0355] DPM: Dipropylene glycol monomethyl ether

[0356] (Molecular weight determination)

[0357] The molecular weights of the polyimide precursor and the polyimide were measured as follows using a room temperature gel permeation chromatography (GPC) apparatus (GPC-101) (manufactured by Showa Denko K.K.) and columns (KD-803, KD-805) (manufactured by Shodex Co.).

[0358] Column temperature: 50°C

[0359] Eluent: N,N'-dimethylformamide (as additive: lithium bromide monohydrate (LiBr·H 2 O) is 30mmol / L (liter), phosphoric acid anhydrous crystals (orthophosphoric acid) is 30mmol / L, tetrahydrofuran (THF) is 10ml / L)

[0360] Flow rate: 1.0ml / min

[0361] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide (molecular weight: about 900,000, 150,000, 100,000, 30,000) (manufactured by Tosoh Corporation) and polyethylene glycol (molecular weight: about 12,000, 4,000 and 1,000) (manufactured by Polymer Laboratories, Inc.)

[0362] (Measurement of Imidization Ratio of Polyimide)

[0363] 20 mg of polyimide powder was placed in an NMR (nuclear magnetic resonance) sample tube (NMR standard sample tube, φ5 (manufactured by Kusano Scientific Co., Ltd.)), and deuterated dimethyl sulfoxide (DMSO-d 6 , 0.05 mass % TMS (tetramethylsilane) mixed product) (0.53 ml), ultrasonic wave was applied to completely dissolve it. The solution was measured by 500 MHz proton NMR using an NMR measuring machine (JNW-ECA500) (manufactured by JEOLDATUM LTD.). The imidization rate was determined as follows: the proton derived from the structure that did not change before and after imidization was determined as a reference proton, and the peak cumulative value of the proton derived from the NH group of the amic acid appearing near 9.5 ppm to 10.0 ppm was used to determine the peak cumulative value of the proton, and the peak cumulative value of the proton derived from the NH group of the amic acid appearing near 9.5 ppm to 10.0 ppm was used to determine it using the following formula.

[0364] Imidization rate (%) = (1-α·x / y) × 100

[0365] In the above formula, x is the peak cumulative value of protons derived from NH groups of amic acid, y is the peak cumulative value of reference protons, and α is the number ratio of reference protons to 1 NH group proton of amic acid in the case of polyamic acid (imidation ratio 0%).

[0366] [Synthesis of polyimide polymers]

[0367] <Synthesis example 1>

[0368] D1 (3.32 g, 16.9 mmol), A1 (3.26 g, 8.57 mmol), B1 (1.04 g, 6.84 mmol) and C2 (0.19 g, 1.76 mmol) were mixed in NEP (23.4 g) and reacted at 40° C. for 8 hours to obtain a polyamic acid solution (1) having a resin solid content concentration of 25% by mass. The number average molecular weight of the polyamic acid was 23,200 and the weight average molecular weight was 70,100.

[0369] <Synthesis example 2>

[0370] D2 (4.29 g, 17.1 mmol), A2 (6.76 g, 17.1 mmol) and B1 (2.61 g, 17.1 mmol) were mixed in NMP (33.9 g), reacted at 50° C. for 2 hours, and then D1 (3.29 g, 16.8 mmol) and NMP (17.0 g) were added and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (2) having a resin solid content concentration of 25% by mass. The number average molecular weight of the polyamic acid was 23,800, and the weight average molecular weight was 69,500.

[0371] <Synthesis example 3>

[0372] NMP was added to the polyamic acid solution (2) (30.5 g) obtained by the synthesis method of Synthesis Example 2 to dilute it to 6% by mass, and then acetic anhydride (3.90 g) and pyridine (2.41 g) were added as imidization catalysts, and the reaction was carried out at 70°C for 2 hours. The reaction solution was put into methanol (460 ml), and the resulting precipitate was filtered out. The precipitate was washed with methanol, and dried under reduced pressure at 100°C to obtain a polyimide powder (3). The imidization rate of the polyimide was 61%, the number average molecular weight was 21,900, and the weight average molecular weight was 59,900.

[0373] <Synthesis Example 4>~Synthesis Example <11>

[0374] Except having changed into the composition shown in Table 1, the same method as Synthesis Examples 2 and 3 was carried out to obtain polyimide powders (4) to (9), (11), and a polyamic acid solution (10) having a resin solid content concentration of 25 mass %.

[0375] The polyimide polymers obtained in Synthesis Examples 1 to 11 are shown in Table 1. In addition, the number average molecular weight and weight average molecular weight of the polyimide powders of Synthesis Examples 4 to 11 are shown in Table 2.

[0376] [Table 1]

[0377] Table 1.

[0378]

[0379] *1 Polyamide acid

[0380] <Synthesis Example 12>

[0381] D1 (19.61 g, 0.1 mol) as a tetracarboxylic acid component and DA-N-A6 (18.73 g, 0.094 mol) as a diamine component were mixed in NMP (345.1 g) and reacted at room temperature for 5 hours to obtain a polyamic acid solution (12) having a resin solid content concentration of 10% by mass. The number average molecular weight of the polyamic acid was 14100 and the weight average molecular weight was 29500.

[0382] <Synthesis Example 13>

[0383] D1 (34.47 g, 0.18 mol) was used as a tetracarboxylic acid component, DA-N-A7 (28.38 g, 0.13 mol) and C3 (16.40 g, 0.057 mol) were used as diamine components, and the mixture was reacted in NMP (713.25 g) at room temperature for 1 hour to obtain a polyamic acid solution (13) having a resin solid content concentration of 10% by mass. The number average molecular weight of the polyamic acid was 13,300 and the weight average molecular weight was 27,800.

[0384] <Synthesis Example 14>

[0385] Using D9 (2.03 g, 7.80 mmol) and D10 (1.02 g, 3.60 mmol) as tetracarboxylic acids, C4 (1.07 g, 3.60 mmol), C1 (0.79 g, 7.20 mmol) and A8 (0.49 g, 1.20 mmol) as diamine components, triethylamine (0.61 g, 0.0060 mol) as a base, and DMT-MM (9.96 g, 36.0 mmol) as a condensing agent, the mixture was reacted in NMP (84.4 g) at room temperature for 3.5 hours to obtain a polyamic acid ester solution.

[0386] This polyamic acid ester solution was put into 550g of methanol, and the precipitated solid was recovered. Furthermore, this solid was washed several times with methanol, and then dried under reduced pressure at 100°C to obtain a powder (14) of polyamic acid ester. The number average molecular weight of this polyamic acid ester was 16,478, and the weight average molecular weight was 39,754.

[0387] <Synthesis Example 15>

[0388] C5 (2.83 g, 18.8 mmol), C4 (5.61 g, 18.8 mmol), and C3 (2.70 g, 9.40 mmol) were added to NMP (126 g) as diamine components, and stirred to dissolve while conveying nitrogen. D1 (8.84 g, 45.1 mmol) was added as a tetracarboxylic acid component while stirring the diamine solution, and NMP was further added to make the resin solid content concentration become 10% by mass, and stirred for 2 hours under a nitrogen atmosphere at room temperature to obtain a polyamic acid solution (15). The number average molecular weight of the polyamic acid was 15,600, and the weight average molecular weight was 38,400.

[0389] <Synthesis Example 16>

[0390] C1 (45.96 g, 0.425 mmol) and C6 (17.80 g, 0.075 mol) were added to NMP (1390 g) as diamine components, and stirred to dissolve them while nitrogen was supplied. D5 (107.83 g, 0.481 mol) was added while stirring the diamine solution, and NMP was further added to make the resin solid content concentration become 10% by mass, and stirred at room temperature for 24 hours to obtain a polyamic acid solution (16). The number average molecular weight of the polyamic acid was 12629, and the weight average molecular weight was 29521.

[0391] <Synthesis Example 17>

[0392] C7 (79.4 g, 0.33 mol) and DA-N-A6 (64.8 g, 0.33 mol) were added as diamine components to NMP (911 g) and GBL (911 g), and stirred to dissolve while nitrogen was supplied. D1 (65.0 g, 0.33 mol) was added while stirring the diamine solution, and after stirring at room temperature for 2 hours, D8 (86.1 g, 0.29 mol) was added, and NMP (390 g) and GBL (390 g) were further added, and stirred at 40° C. under a nitrogen atmosphere for 30 hours to obtain a polyamic acid solution (17) having a resin solid content concentration of 10%. The number average molecular weight of the polyamic acid solution was 15,773, and the weight average molecular weight was 31,242.

[0393] [Table 2]

[0394] Table 2.

[0395]

[0396] *1 Polyamide acid

[0397] *2 Polyamic acid ester

[0398] <Synthesis Example 18>

[0399] D4 (30.03 g, 0.100 mol) as a tetracarboxylic acid component, C1 (9.19 g, 0.085 mol) and A6 (5.23 g, 0.015 mol) as diamine components were reacted in NMP (252 g) at 50° C. for 24 hours to prepare a polyamic acid solution having a resin solid content concentration of 15% by mass.

[0400] NMP was added to 50 g of the polyamic acid solution to dilute it to 5% by mass, and pyridine (8.0 g) and acetic anhydride (17.2 g) were further added as imidization catalysts, and the mixture was reacted at 40° C. for 3 hours. The solution was poured into 600 ml of methanol, and the resulting precipitate was filtered out and dried to obtain a white polyimide powder (18). The imidization rate of the polyimide was 83%, the number average molecular weight was 9,834, and the weight average molecular weight was 21,659.

[0401] <Synthesis Example 19>

[0402] D1 (9.81 g, 0.05 mol) and D7 (9.60 g, 0.044 mol) as tetracarboxylic acid components and C8 (19.83 g, 0.100 mol) as diamine components were reacted in NMP (222 g) at room temperature for 5 hours to prepare a polyamic acid solution (19) having a resin solid content concentration of 15% by mass. The number average molecular weight of the polyamic acid was 10,893 and the weight average molecular weight was 25,972.

[0403] [Table 3]

[0404] Table 3.

[0405]

[0406] *1 Polyamide acid

[0407] [Preparation of Liquid Crystal Alignment Agent]

[0408] The examples of preparing the liquid crystal aligning agent are described in the examples and comparative examples. Using the liquid crystal aligning agents obtained in the examples and comparative examples, "production of liquid crystal display elements", "evaluation of liquid crystal orientation", "evaluation of adhesion of liquid crystal aligning films" or "peeling test" were performed.

[0409] [Production of Liquid Crystal Display Element]

[0410] (Production of Vertically Aligned Liquid Crystal Display Element)

[0411] The liquid crystal alignment agents (V-1) to (V-9) obtained in the examples and the liquid crystal alignment agents (R-V1) to (R-V2) obtained in the comparative examples were filtered under pressure using a membrane filter having a pore size of 1 μm. The obtained solution was spin-coated on the ITO surface of a 100×100 mm glass substrate with an ITO electrode (vertical: 100 mm, horizontal: 100 mm, thickness: 0.7 mm) washed with pure water and IPA (isopropyl alcohol), and heated on a hot plate at 100°C for 2 minutes, and heated at 210°C for 10 minutes in a heat circulation type clean oven, thereby obtaining an ITO substrate with a liquid crystal alignment film having a film thickness of 100 nm. Two ITO substrates with liquid crystal alignment films were prepared, and a 6 μm spacer was applied to the surface of the liquid crystal alignment film of one of the substrates.

[0412] Next, the periphery was coated with a sealant (XN-1500T manufactured by Kyoritsu Chemical). After that, the liquid crystal composition (LC-V1) was dropped onto the surface of the liquid crystal alignment film of the substrate by the ODF (One Drop Filling) method, and then another substrate was attached in such a way that the liquid crystal alignment film interface was opposite, and the sealant was cured to obtain a vertical alignment type liquid crystal display element. The obtained liquid crystal display element was heated at 110°C for 1 hour, and then left at room temperature for one night before being used for each evaluation.

[0413] (Fabrication of FFS Type Liquid Crystal Display Element)

[0414] <Brushing Orientation Treatment>

[0415] The liquid crystal aligning agents (I-10) to (I-13), (I-15) to (I-18) obtained in the examples and the liquid crystal aligning agents (R-I3) to (R-I4) obtained in the comparative examples were filtered under pressure using a membrane filter having a pore size of 1 μm.

[0416] Next, a substrate with an electrode described in paragraphs

[0060] to

[0062] of International Publication (WO2014-084364) and a glass substrate having an ITO film formed on the back surface and columnar spacers with a height of 4 μm were prepared and washed with pure water and IPA (isopropyl alcohol).

[0417] The liquid crystal aligning agent after pressure filtration was spin-coated on the substrate, and heat-treated on a hot plate at 80° C. for 2 minutes, and heat-treated in a heat circulation clean oven at 230° C. for 30 minutes, thereby obtaining a coating substrate with a film thickness of 100 nm.

[0418] The coated substrate was brushed with rayon cloth (YA-20R manufactured by Yoshikawa Chemical Industry) (roller diameter: 120 nm, roller rotation speed: 1000 rpm, moving speed: 20 mm / sec, pressing length: 0.4 mm), then ultrasonically treated in pure water for 1 minute for cleaning, water droplets were removed by blowing, and then dried at 80°C for 15 minutes to obtain a substrate with a liquid crystal orientation film.

[0419] The above two substrates were used as a set, and a sealant was printed on the substrate. After the other substrate was attached in a manner that the surfaces of the liquid crystal alignment films were opposite and the orientation direction was 0°, the sealant was cured. Then, the liquid crystal composition (LC-I1) was injected by a reduced pressure injection method, and the injection port was sealed to obtain an FFS type liquid crystal display element. The obtained liquid crystal display element was heated at 110°C for 1 hour, left at room temperature overnight, and used for each evaluation.

[0420] <Photo-Alignment Treatment>

[0421] The liquid-crystal aligning agent (I-14) obtained in the Example was filtered under pressure using a membrane filter having a pore size of 1 μm.

[0422] Next, a substrate with an electrode described in paragraphs

[0060] to

[0062] of International Publication (WO2014-084364) and a glass substrate having an ITO film formed on the back surface and columnar spacers with a height of 4 μm were prepared and washed with pure water and IPA (isopropyl alcohol).

[0423] The liquid crystal aligning agent after pressure filtration was spin-coated on the substrate, and heat-treated on a hot plate at 80° C. for 2 minutes, and heat-treated in a heat circulation clean oven at 230° C. for 30 minutes, thereby obtaining a coating substrate with a film thickness of 100 nm.

[0424] The coating surface of the coating substrate was irradiated with 800 mJ / cm2 of linearly polarized ultraviolet light with an extinction ratio of 26:1 and a wavelength of 254 nm. 2 . The substrate was heat treated at 230°C for 30 minutes in a heat circulation clean oven to obtain a substrate with a liquid crystal alignment film. The above two substrates were taken as a group, and a sealant was printed on the substrate. Another substrate was attached in a manner that the surfaces of the liquid crystal alignment films were opposite and the orientation direction was 0°, and then the sealant was cured. Then, liquid crystal (LC-I2) was injected by a reduced pressure injection method, and the injection port was sealed to obtain an FFS type liquid crystal display element. The obtained liquid crystal display element was heated at 110°C for 1 hour, left at room temperature overnight, and used for each evaluation.

[0425] [Evaluation of Liquid Crystal Display Element]

[0426] (Liquid Crystal Orientation)

[0427] The liquid crystal orientation of the liquid crystal display element was observed with a polarizing microscope (ECLIPSE E600WPOL) (manufactured by Nikon Corporation) to confirm whether the liquid crystal was horizontally oriented or vertically oriented. Specifically, a liquid crystal display element in which a defect due to liquid crystal flow was not observed is considered to be good.

[0428] Table 3 shows the evaluation results of the liquid-crystal orientation of the liquid crystal display element in a lump.

[0429] (Adhesion of Liquid Crystal Alignment Film)

[0430] The liquid crystal aligning agents (V-1) to (V-6), (I-7) to (I-13) obtained in the examples and the liquid crystal aligning agents (R-V1) to (R-V2) obtained in the comparative examples were filtered under pressure using a membrane filter having a pore size of 1 μm. The liquid crystal aligning agents were applied to a 100×100 mm glass substrate with an ITO electrode (vertical: 100 mm, horizontal: 100 mm, thickness: 0.7 mm) washed with pure water and IPA (isopropyl alcohol), and heated on a hot plate at 80° C. for 2 minutes. Except for Comparative Examples 3 and 7, the liquid crystal aligning agents were heated at 120° C. for 10 minutes in a heat circulation clean oven. In Comparative Examples 3 and 7, the liquid crystal aligning agents were heated at 210° C. for 10 minutes, thereby preparing an ITO substrate with a liquid crystal aligning film having a film thickness of 100 nm. A 6μm bead spacer was applied on one substrate, and a sealant (XN-1500T manufactured by Kyoritsu Chemical) was printed on the liquid crystal alignment film of the other substrate. The substrates were bonded together so that the overlap width of the substrates was 1 cm. At this time, the amount of sealant was adjusted so that the diameter of the sealant after bonding was 3 mm. The two bonded substrates were fixed with a clamp and then thermally cured at 150°C for 1 hour to prepare the test sample substrate for this evaluation.

[0431] After that, the ends of the upper and lower substrates of the test sample substrate were fixed using a desktop precision universal testing machine (AGS-X 500N) (manufactured by Shimadzu Corporation), and then pressed from the upper part of the center of the substrate to measure the stress (N) during peeling, i.e., the peeling stress (N).

[0432] In the evaluation, the larger the value of the peel stress (N), the better the adhesion with the sealant and the base substrate (the values ​​of the peel stress (N) are shown in Table 3).

[0433] <Example 1>

[0434] NEP (22.7 g) and BCS (20.8 g) were added to the polyamic acid solution (1) (7.43 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 1, and the mixture was stirred at 50° C. for 5 hours. MA-M1 (0.56 g) was then added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (V-1). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0435] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (V-1).

[0436] Liquid crystal display elements were prepared and various evaluations were performed in the same manner on the following Examples 2 to 16 and Comparative Examples 1 to 8. The results of the Examples and Comparative Examples are summarized and shown in Table 3.

[0437] <Example 2>

[0438] NMP (27.3 g) and BCS (25.5 g) were added to the polyamic acid solution (2) (9.80 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 2, and the mixture was stirred at 50° C. for 5 hours. Then, G-M1 (0.74 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (V-2). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0439] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (V-2).

[0440] <Example 3>

[0441] The peeling test was performed using the liquid-crystal aligning agent obtained in Example 2.

[0442] <Example 4>

[0443] NMP (35.4 g) and BCS (24.2 g) were added to the polyimide powder (3) (2.33 g) obtained in Synthesis Example 3, and the mixture was stirred at 70° C. for 24 hours to dissolve. Then, MA-M1 (0.23 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (V-3). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0444] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (V-3).

[0445] <Example 5>

[0446] The peeling test was performed using the liquid-crystal aligning agent (V-3) obtained in Example 4.

[0447] <Example 6>

[0448] NEP (32.8 g) and PB (18.2 g) were added to the polyimide powder (3) (1.86 g) obtained in Synthesis Example 3, and the mixture was stirred at 70° C. for 24 hours to dissolve. Then, MA-M1 (0.09 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (V-4). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0449] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (V-4).

[0450] <Example 7>

[0451] γ-BL (6.40 g) and PGME (42.5 g) were added to the polyimide powder (3) (1.65 g) obtained in Synthesis Example 3, and the mixture was stirred at 70° C. for 24 hours to dissolve the mixture. Then, G-M1 (0.08 g) and K1 (0.08 g) were added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (V-5). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0452] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (V-5).

[0453] <Example 8>

[0454] NEP (34.0 g), BCS (12.4 g) and PB (14.6 g) were added to the polyimide powder (4) (2.55 g) obtained in Synthesis Example 4, and the mixture was stirred at 70° C. for 24 hours to dissolve. Then, MA-M1 (0.08 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (V-6). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0455] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (V-6).

[0456] <Example 9>

[0457] γ-BL (6.40 g) and PGME (42.5 g) were added to the polyimide powder (3) (1.65 g) obtained in Synthesis Example 3, and the mixture was stirred at 70° C. for 24 hours to dissolve. Then, MA-M1 (0.05 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (V-7). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0458] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (V-7).

[0459] <Example 10>

[0460] γ-BL (6.40 g) and PGME (42.5 g) were added to the polyimide powder (3) (1.65 g) obtained in Synthesis Example 3, and the mixture was stirred at 70° C. for 24 hours to dissolve the mixture. Then, MA-M1 (0.08 g) and K1 (0.08 g) were added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (V-8). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0461] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (V-8).

[0462] <Example 11>

[0463] γ-BL (6.40 g) and PGME (42.5 g) were added to the polyimide powder (3) (1.65 g) obtained in Synthesis Example 3, and the mixture was stirred at 70° C. for 24 hours to dissolve the mixture. Then, MA-M1 (0.08 g) and G-M1 (0.08 g) were added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (V-9). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0464] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (V-9).

[0465] <Example 12>

[0466] GBL (6.00 g), DMI (6.00 g), and EEP (8.00 g) were added to the polyamic acid solution (12) (20.0 g) having a resin solid content concentration of 10% by mass obtained in Synthesis Example 12, and the mixture was stirred at 50° C. for 5 hours. Then, MA-M1 (0.60 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (I-10). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0467] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (I-10).

[0468] <Example 13>

[0469] GBL (12.0 g) and DEDE (8.00 g) were added to the polyamic acid solution (13) (20.0 g) having a resin solid content concentration of 10% by mass obtained in Synthesis Example 13, and the mixture was stirred at 50° C. for 5 hours. Then, G-M1 (0.60 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (I-11). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0470] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (I-11).

[0471] <Example 14>

[0472] GBL (30.0 g) and DME (8.00 g) were added to the powder (14) (2.0 g) of the polyamic acid ester obtained in Synthesis Example 14, and the mixture was stirred at 50° C. for 5 hours. Then, MA-M1 (0.20 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (I-12). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0473] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (I-12).

[0474] <Example 15>

[0475] GBL (12.0 g) and DEME (8.00 g) were added to the polyamic acid solution (15) (20.0 g) having a resin solid content concentration of 10% by mass obtained in Synthesis Example 15, and the mixture was stirred at 50° C. for 5 hours. Then, G-M1 (0.20 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (I-13). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0476] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (I-13).

[0477] <Example 16>

[0478] GBL (12.0 g) and DEME (8.00 g) were added to the polyamic acid solution (16) (20.0 g) having a resin solid content concentration of 10% by mass obtained in Synthesis Example 16, and the mixture was stirred at 50° C. for 5 hours. Then, MA-M1 (0.10 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (I-14). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0479] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (I-14).

[0480] <Example 17>

[0481] GBL (16.0 g) and DPM (4.00 g) were added to the polyamic acid solution (17) (20.0 g) having a resin solid content concentration of 10% by mass obtained in Synthesis Example 17, and stirred at 50° C. for 5 hours. Then, G-M1 (0.10 g) was added to the solution, and stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (I-15). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0482] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (I-15).

[0483] <Example 18> to <Example 20>

[0484] Liquid crystal aligning agents (I-16) to (I-18) were obtained by adding an adhesive compound and other adhesive compounds in the same manner as in Example 17 according to the composition shown in Table 3. Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0485] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agents (I-16) to (I-18).

[0486] <Example 21>

[0487] Except having used K2 instead of K1, the liquid crystal aligning agent (V-19) was obtained by the same method as in Example 7. In this liquid-crystal aligning agent, abnormality, such as turbidity and precipitation, was not observed, and it was confirmed that it was a uniform solution.

[0488] Preparation of a liquid crystal display element, evaluation of liquid crystal orientation, and evaluation of adhesion of a liquid crystal aligning film were performed using the obtained liquid crystal aligning agent (V-19).

[0489] <Example 22>

[0490] Except having used K2 instead of K1, the liquid crystal aligning agent (V-20) was obtained by the same method as in Example 10. In this liquid-crystal aligning agent, abnormalities such as turbidity and precipitation were not observed, and it was confirmed that it was a uniform solution.

[0491] Preparation of a liquid crystal display element, evaluation of liquid crystal orientation, and evaluation of adhesion of a liquid crystal aligning film were performed using the obtained liquid crystal aligning agent (V-20).

[0492] <Example 23>

[0493] 3.00 g of the polyimide powder (18) obtained in Synthesis Example 18 was dissolved in GBL (34.50 g) by stirring at 50° C. for 20 hours.

[0494] GBL was further added so that the concentration of the polyimide in the solution became 6 mass %, and the solution was stirred at 50° C. for 20 hours.

[0495] NMP, GBL and BCS were added to the polyamic acid solution (19) (40.0 g) having a resin solid content concentration of 15% by mass obtained in Synthesis Example 19 to prepare a solution containing 6% by mass of polyamic acid, 20% by mass of NMP, 59% by mass of GBL and 15% by mass of BCS.

[0496] 20 g of the polyimide solution prepared as described above was mixed with 80 g of the diluted polyamic acid solution, stirred at room temperature for 20 hours, and G-M1 (0.30 g) was further added to obtain a liquid crystal aligning agent (T-20). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0497] Using the obtained liquid crystal orientation agent (T-21), a liquid crystal display element and a substrate for adhesion evaluation are obtained in the same manner as in Example 16, except that the bonding is performed in an orientation direction of 90°. The liquid crystal display element is produced, the liquid crystal orientation is evaluated, and the adhesion of the liquid crystal orientation film is evaluated.

[0498] <Example 24>

[0499] Except having used MA-M1 instead of G-M1, the liquid-crystal aligning agent (T-22) was obtained in the same manner as in Example 23. Abnormalities such as turbidity and precipitation were not observed in the liquid-crystal aligning agent, and it was confirmed to be a uniform solution.

[0500] Preparation of a liquid crystal display element, evaluation of the liquid crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid crystal aligning agent (T-22).

[0501] <Comparative Example 1>

[0502] NEP (22.7 g) and BCS (20.8 g) were added to the polyamic acid solution (1) (7.43 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 1, and the mixture was stirred at 50° C. for 5 hours to obtain a liquid crystal aligning agent (R-V1). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0503] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (R-V1).

[0504] <Comparative Example 2>

[0505] NEP (22.7 g) and BCS (20.8 g) were added to the polyamic acid solution (1) (7.43 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 1, and the mixture was stirred at 50° C. for 5 hours. Then, K1 (0.18 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (R-V2). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0506] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (R-V2).

[0507] <Comparative Example 3>

[0508] Preparation of a liquid crystal display element, evaluation of liquid crystal orientation, and evaluation of adhesion of a liquid crystal aligning film were performed in the same manner as in Comparative Example 2, except that the temperature of the heat circulation clean oven was set to 210° C. and the heat treatment was performed for 10 minutes.

[0509] <Comparative Example 4>

[0510] The peel test was performed using the liquid-crystal aligning agent obtained in the manner of Comparative Example 1.

[0511] <Comparative Example 5>

[0512] GBL (6.00 g), DMI (6.00 g) and EEP (8.00 g) were added to the polyamic acid solution (12) (20.0 g) having a resin solid content concentration of 10% by mass obtained in Synthesis Example 12, and the mixture was stirred at 50° C. for 5 hours to obtain a liquid crystal aligning agent (R-I3). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0513] A peel test was performed using the obtained liquid-crystal aligning agent (R-I3).

[0514] <Comparative Example 6>

[0515] GBL (6.00 g), DMI (6.00 g), and EEP (8.00 g) were added to the polyamic acid solution (12) (20.0 g) having a resin solid content concentration of 10% by mass obtained in Synthesis Example 12, and stirred at 50° C. for 5 hours. Then, K1 (0.20 g) was added to the solution, and stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (R-I4). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0516] Preparation of a liquid crystal display element, evaluation of the liquid crystal orientation, and evaluation of the adhesion of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (R-I4).

[0517] <Comparative Example 7>

[0518] Preparation of a liquid crystal display element, evaluation of liquid crystal orientation, and evaluation of adhesion of a liquid crystal aligning film were performed in the same manner as in Comparative Example 6, except that the temperature of the heat circulation clean oven was set to 210° C. and the heat treatment was performed for 10 minutes.

[0519] <Comparative Example 8>

[0520] GBL (6.00 g), DMI (6.00 g) and EEP (8.00 g) were added to the polyamic acid solution (12) (20.0 g) having a resin solid content concentration of 10% by mass obtained in Synthesis Example 12, and the mixture was stirred at 50° C. for 5 hours. Then, K1 (0.60 g) was added to the solution, and the mixture was stirred at 25° C. for 2 hours to obtain a liquid crystal aligning agent (R-I5). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0521] The obtained liquid crystal aligning agent (R-I5) was used to prepare a liquid crystal display element, evaluate the liquid crystal orientation, and evaluate the adhesion of a liquid crystal aligning film. In addition, a peeling test was performed on Examples 3 and 5 and Comparative Example 4. The peeling test was as follows.

[0522] <Comparative Example 9>

[0523] Except not adding G-M1, the liquid crystal aligning agent (R-T6) was obtained in the same manner as in Example 23. Abnormalities such as turbidity and precipitation were not observed in the alignment agent, and it was confirmed to be a uniform solution.

[0524] Preparation of a liquid crystal display element, evaluation of the liquid-crystal orientation, and adhesion evaluation of a liquid crystal aligning film were performed using the obtained liquid-crystal aligning agent (R-T6).

[0525] <Peel test>

[0526] The liquid crystal aligning agent ( ) obtained in the example and the liquid crystal aligning agent ( ) obtained in the comparative example were pressure-filtered using a membrane filter having a pore diameter of 1 μm.

[0527] The liquid crystal orientation treating agent is applied onto a 100×100 mm PET film substrate with an ITO electrode (length: 100 mm, width: 100 mm, thickness: 50 um), and after heating treatment on a heating plate at 120°C for 5 minutes, it is cut into a size of 100×20 mm to prepare two ITO substrates with a liquid crystal orientation film with a film thickness of 100 nm.

[0528] A 30 μm bead spacer was applied on one substrate, and a sealant (Mitsui Chemicals 723K1) was printed on the liquid crystal alignment film of the other substrate, and the substrates were laminated in an overlapping manner. The amount of the sealant was adjusted so that the area of ​​the sealant after lamination was 50×10 mm.

[0529] Fix the two bonded substrates with a clamp and irradiate with 3J / cm 2 The test sample substrates used in this evaluation were prepared by exposure to ultraviolet light, followed by thermal curing at 120°C for 1 hour.

[0530] Then, the ends of the upper and lower substrates of the test sample substrate were fixed using a table-top precision universal testing machine (AGS-X 500N) (manufactured by Shimadzu Corporation), and the stress (N / 25 mm) when pulled upward, i.e., the peel strength (N / 25 mm) was measured.

[0531] In the evaluation, the larger the value of the peel strength (N / 25 mm), the better the adhesion between the sealant and the base substrate (the values ​​of the peel strength (N / 25 mm) are shown in Table 3).

[0532] [Table 4]

[0533] Table 4

[0534]

[0535] ※1 represents the amount of each polymer introduced relative to 100 parts by weight of all polymers (parts by weight)

[0536] ※2 represents the amount of the (other) adhesive compound introduced relative to 100 parts by weight of the total polymer (parts by weight). ※3 The temperature of the heat circulation clean oven was set to 210°C, and the heating treatment was performed for 10 minutes.

[0537] [Table 5]

[0538] Table 4 follow-up

[0539]

[0540] *1 represents the amount of each polymer introduced (parts by weight) relative to 100 parts by weight of all polymers.

[0541] *2 represents the amount (parts by weight) of the (other) adhesive polymer introduced relative to 100 parts by weight of all polymers.

[0542] ※3 The temperature of the heat circulation cleaning oven was set to 210°C and the heating treatment was performed for 10 minutes.

[0543] From the above results, it is understood that the liquid crystal display element using the liquid crystal aligning film obtained from the liquid crystal aligning agent of the present invention has good liquid crystal orientation and also shows a high adhesion compared with the liquid crystal aligning film obtained from the liquid crystal aligning agent of the comparative example.

[0544] Specifically, the Examples of the present invention including the adhesion compound and the Comparative Examples not including the adhesion compound were compared, that is, Example 1 and Comparative Example 1, and Example 12 and Comparative Examples 6 to 8.

[0545] In addition, compared with the liquid crystal alignment film obtained by using the liquid crystal alignment agent having a diamine having a vertical alignment property (side chain diamine in the table), the liquid crystal alignment film obtained by using the liquid crystal alignment agent having a horizontal alignment property (main chain diamine) has a high adhesion result. Specifically, see the comparison between Example 1 and Example 12.

[0546] Moreover, when other adhesive compounds are introduced into the liquid crystal aligning agent of the present invention, a liquid crystal display element having more excellent adhesiveness with the liquid crystal aligning film is formed.

[0547] Industrial Applicability

[0548] The liquid crystal display element using the liquid crystal alignment film obtained by the liquid crystal alignment agent of the present invention can be applied to display elements of various liquid crystal modes. In addition, these elements can also be used in liquid crystal displays for display purposes, and dimming windows and light shutters for controlling the transmission and blocking of light.

Claims

1. A liquid crystal alignment agent, characterized in that: Contains the following components (A), (B) and (C), The amount of component (B) is 10 to 30 parts by weight relative to 100 parts by weight of component (A). (A) component: a polymer obtained by reacting a tetracarboxylic acid derivative with a diamine, wherein the tetracarboxylic acid derivative is at least one selected from the group consisting of tetracarboxylic dianhydride, tetracarboxylic acid diester and tetracarboxylic acid diester dihalide, The tetracarboxylic acid derivative includes a compound having at least one selected from the group consisting of a cyclobutane ring structure, a cyclopentane ring structure, a cyclohexane ring structure, and a benzene ring structure, The diamine comprises a diamine selected from p-phenylenediamine, m-phenylenediamine, 1,5-bis(4-aminophenoxy)pentane, 1,3-bis(4-aminophenethyl)urea, 4-(2-(methylamino)ethyl)aniline, a compound represented by the following formula [C6], 1,2-bis(4-aminophenoxy)ethane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylamine and bis(4-aminophenyl)-N-methylamine; (B) component: at least one compound selected from the group consisting of the following formula [G-M1] to formula [G-M4]; as well as (C) Organic solvent.

2. The liquid crystal alignment agent according to claim 1, wherein The component (B) is of the formula [G-M1].

3. The liquid crystal aligning agent according to claim 1 or 2, wherein: The component (C) has at least one selected from the group consisting of the following formulas (Sol-1) and (Sol-2), In the formula (Sol-1), Y s 7 and Y s 8 are each independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms, X s 1 is an oxygen atom or -COO-, X s 2 is a single bond or a carbonyl group, R s 7 is an alkanediyl group having 2 to 4 carbon atoms, n s 1 is an integer from 1 to 3, where n s 1 If the value is 2 or 3, multiple R s 7 Optional: same or different; In the formula (Sol-2), Z s 1 is a divalent hydrocarbon group having 1 to 6 carbon atoms, Y s 9 and Y s 10 Each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms. 4 . A liquid crystal alignment film formed using the liquid crystal aligning agent according to claim 1 .

5. A method for manufacturing a liquid crystal alignment film, comprising: A step of coating the liquid crystal alignment agent according to any one of claims 1 to 3 on a substrate to form a coating film; and a step of irradiating the coating film with light in a state where the coating film is not in contact with the liquid crystal layer or in a state where the coating film is in contact with the liquid crystal layer. 6 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 4 or the liquid crystal alignment film obtained by the production method according to claim 5 .

Citation Information

Patent Citations

  • Liquid crystal orientation layer

    JP1999119225A

  • Liquid crystal aligning agent and liquid crystal display element

    JP2010097188A

  • Liquid crystal aligning agent, liquid crystal aligning layer, method for forming liquid crystal aligning layer, and liquid crystal display element

    JP2013113937A

  • Liquid crystal aligning agent, method for forming liquid crystal alignment film, and liquid crystal display device

    WO2009025386A1

  • Liquid-crystal alignment material and liquid-crystal display element made with the same

    WO2009093707A1